Adhesive composition, adhesive layer, adhesive sheet, optical member with adhesive layer, image display device, and touch panel
By using an acrylic adhesive composition that adjusts the moisture content under specific conditions, the problem of white turbidity of the adhesive layer under high temperature humidification conditions is solved, and the visual recognition of the image display device is maintained.
Patent Information
- Application Number
- CN202380060503.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-19
- Filing Date
- 2023-08-14
- Publication Date
- 2025-03-28
AI Technical Summary
Under high temperature humidification conditions, the adhesive layer is prone to white turbidity, resulting in a decrease in visual recognition of the image display device.
An acrylic adhesive composition is used that adjusts its moisture content under certain conditions to ensure that white cloudiness is not prone to occur even under high temperature humidification conditions. The specific method includes 23°C and 50%RH conditions for 24 hours, and 85%RH conditions for 8 hours, and 23°C and 50%RH conditions for 24 hours, so that W2/W1 is greater than 1.
By using the adhesive layer formed by the acrylic adhesive composition, the visual recognition of the image display device can be maintained under high temperature humidification conditions, and the occurrence of white turbidity can be avoided.
Smart Images

Figure CN119731284A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an adhesive composition, an adhesive layer, an adhesive sheet, an optical member with an adhesive layer, an image display device, and a touch panel. Background Art
[0002] In recent years, image display devices such as liquid crystal displays (LCDs) and organic electroluminescent displays (OLEDs), and touch panels in which touch sensors are assembled in these image display devices are widely used in various fields. Such image display devices and touch panels have a structure in which various optical components such as a polarizing film, a phase difference film, an optical compensation film, a touch sensor film, and a cover film are stacked on the image display panel. In the use of bonding these optical components, an adhesive sheet having an adhesive layer is used. For example, in the bonding of various optical components in an image display device, a transparent adhesive sheet is used (for example, refer to patent documents 1 to 3).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2003-238915
[0006] Patent Document 2: Japanese Patent Application Publication No. 2003-342542
[0007] Patent Document 3: Japanese Patent Application Publication No. 2004-231723 Summary of the invention
[0008] Problems to be solved by the invention
[0009] In the bonding of the above optical components, an optical component with an adhesive layer having an adhesive sheet attached to the optical component is generally used. When the optical component with an adhesive layer is bonded to a glass substrate, for example, after being placed under high temperature and high humidity conditions such as 85°C and 85%RH and then restored to room temperature, the adhesive layer sometimes becomes white turbid (humidified white turbidity). When humidified white turbidity occurs, it becomes a cause of reduced visual recognition of the image display device.
[0010] Therefore, an object of the present invention is to provide an acrylic pressure-sensitive adhesive composition for forming a pressure-sensitive adhesive layer used for bonding optical members of an image display device, and capable of forming a pressure-sensitive adhesive layer that is less likely to become white turbid under high-temperature and humid conditions.
[0011] Another object of the present invention is to provide a pressure-sensitive adhesive layer that is less likely to become turbid even under high-temperature and humid conditions.
[0012] Another object of the present invention is to provide a PSA sheet having a PSA layer that is less likely to produce white turbidity due to humidity even under high-temperature and humid conditions.
[0013] Another object of the present invention is to provide an optical member with a pressure-sensitive adhesive layer having a pressure-sensitive adhesive layer that is less likely to produce white turbidity due to humidity even under high-temperature and humidification conditions.
[0014] Another object of the present invention is to provide a high-performance image display device and a touch panel including the above-mentioned pressure-sensitive adhesive layer-attached optical member and in which visibility is unlikely to decrease even under high-temperature and humid conditions.
[0015] Means used to solve problems
[0016] The first aspect of the present invention provides an acrylic adhesive composition for forming an adhesive layer used for bonding an optical member of an image display device. In this specification, the acrylic adhesive composition of the first aspect of the present invention is sometimes referred to as "the acrylic adhesive composition of the present invention" or simply "the adhesive composition of the present invention".
[0017] The acrylic adhesive composition of the present invention is used for attaching optical components such as polarizing films, retardation films, optical compensation films, touch sensor films, and cover films to image display panels in image display devices such as liquid crystal displays (LCDs) and organic electroluminescent displays (OLEDs), and touch panels in which touch sensors are incorporated in these image display devices, or for forming an adhesive layer used for attaching these optical components to each other.
[0018] In the bonding of the above optical components, an optical component with an adhesive layer having an adhesive sheet attached to the optical component is generally used. When the optical component with an adhesive layer is bonded to a glass substrate, for example, after being placed under high temperature and high humidity conditions such as 85°C and 85%RH and then restored to room temperature, the adhesive layer sometimes becomes white turbid (humidified white turbidity). When humidified white turbidity occurs, it becomes a cause of reduced visual recognition of the image display device.
[0019] In the acrylic pressure-sensitive adhesive composition of the present invention, the water contents W1 and W2 after the pressure-sensitive adhesive layer is subjected to the following conditions (A) and (B) satisfy the following formula (1).
[0020] W2 / W1>1 …… (1)
[0021] (A) Water content of the adhesive layer after being stored at 23°C and 50% RH for 24 hours: W1 (μg / cm 2 )
[0022] (B) Water content of the adhesive layer after (A) when it was stored at 85°C and 85% RH for 8 hours and then at 23°C and 50% RH for 24 hours: W2 (μg / cm 2 )
[0023] The water contents W1 and W2 satisfy the above formula (1). That is, the water content W2 is greater than the water content W1. This configuration is preferred from the following viewpoints: even if the adhesive layer is placed under high temperature and high humidity conditions and then restored to room temperature, it is not easy to produce humidified white turbidity, and the visual recognizability of the image display device can be maintained.
[0024] In the acrylic pressure-sensitive adhesive composition of the present invention, the water contents W1 and W3 after the pressure-sensitive adhesive layer is subjected to the following conditions (A) and (C) preferably satisfy the following formula (2).
[0025] W3 / W1>2.3 …… (2)
[0026] (A) Water content of the adhesive layer after being stored at 23°C and 50% RH for 24 hours: W1 (μg / cm 2 )
[0027] (C) Water content of the adhesive layer after (A) after being stored at 85°C and 85% RH for 8 hours: W3 (μg / cm 2 )
[0028] The structure in which the above-mentioned W3 / W1 satisfies the above-mentioned formula (2), that is, the above-mentioned W3 / W1 is greater than 2.3 is preferred from the following viewpoints: the above-mentioned W2 / W1 easily satisfies the above-mentioned formula (1), and even if the above-mentioned adhesive layer is placed under high temperature and high humidity conditions and then restored to room temperature, it is not easy to produce humidified white turbidity, and the visual recognizability of the image display device can be maintained.
[0029] The acrylic adhesive composition of the present invention preferably contains an acrylic polymer, and the acrylic polymer contains 10 to 40 parts by weight of a functional group-containing monomer relative to the total amount (100 parts by weight) of the monomer components constituting the acrylic polymer. This configuration is preferred from the following viewpoints: the W2 / W1 easily satisfies the formula (1), and even if the adhesive layer is placed under high temperature and high humidity conditions of 85°C and 85%RH and then restored to room temperature, it is not easy to produce humidified white turbidity, and the visual recognition of the image display device can be maintained.
[0030] The acrylic adhesive composition of the present invention preferably has a halogen ion concentration of 50 ppm or less. This configuration is preferred from the viewpoint of obtaining an anticorrosive effect on metal wiring in a touch panel having an optical member (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film bonded thereto.
[0031] The second aspect of the present invention provides an adhesive layer formed from the acrylic adhesive composition of the present invention. In this specification, the adhesive layer of the second aspect of the present invention is sometimes referred to as "the adhesive layer of the present invention". The adhesive layer of the present invention is formed from the acrylic adhesive composition of the present invention, and is therefore preferably formed from the viewpoint of not easily generating humidified white turbidity even when placed under high temperature and high humidity conditions and returned to room temperature, thereby maintaining the visual recognition of the image display device.
[0032] The dielectric constant of the adhesive layer of the present invention at a frequency of 100 kHz is preferably 4 or less. This configuration is preferred from the viewpoint that the insulation resistance of the adhesive layer is improved, and in a touch panel to which an optical member (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is bonded, erroneous operation of touch operation caused by electrical noise can be suppressed.
[0033] The third aspect of the present invention provides an adhesive sheet having an adhesive layer of the present invention. In this specification, the adhesive sheet of the third aspect of the present invention is sometimes referred to as "the adhesive sheet of the present invention". The adhesive sheet of the present invention has the adhesive layer of the present invention, and is therefore preferred from the viewpoint that humidified white turbidity is not easily generated even after being placed under high temperature and high humidity conditions and returned to room temperature, and the visual recognizability of the image display device can be maintained.
[0034] The fourth aspect of the present invention provides an optical component with an adhesive layer having the adhesive sheet of the present invention adhered to at least one surface of the optical component. In this specification, the optical component with an adhesive layer of the fourth aspect of the present invention is sometimes referred to as "the optical component with an adhesive layer of the present invention". The optical component with an adhesive layer of the present invention has the adhesive layer of the present invention, and is therefore preferred from the viewpoint of not easily generating humidified white turbidity even after being placed under high temperature and high humidity conditions and returning to room temperature, and being able to maintain the visual recognizability of the image display device.
[0035] The fifth aspect of the present invention provides an image display device having the optical member with a pressure-sensitive adhesive layer of the present invention. In this specification, the image display device of the fifth aspect of the present invention may be referred to as "the image display device of the present invention." The image display device of the present invention may be a touch panel.
[0036] The image display device and touch panel of the present invention are obtained by bonding an optical member using the pressure-sensitive adhesive layer of the present invention, and therefore are preferred from the viewpoint that visibility is unlikely to decrease even under high-temperature and humid conditions.
[0037] Effects of the Invention
[0038] The acrylic adhesive composition of the present invention can form an adhesive layer that is not prone to white turbidity due to humidity even when placed under high temperature and humidity conditions and then returned to room temperature. Therefore, by bonding optical components using an adhesive sheet having an adhesive layer formed from the acrylic adhesive composition of the present invention, a high-performance image display device and touch panel whose visual recognition is not easily reduced even under high temperature and humidity conditions can be effectively manufactured. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 It is a schematic diagram showing a specific example of a preferred embodiment of the pressure-sensitive adhesive sheet of the present invention.
[0040] Figure 2 It is a schematic diagram which shows the specific example of the preferable aspect of the optical member with an adhesive layer of this invention.
[0041] Figure 3 It is a schematic diagram showing a specific example of a preferred embodiment of the image display device of the present invention.
[0042] Figure 4 It is a schematic diagram showing a specific example of a preferred embodiment of the touch panel of the present invention. DETAILED DESCRIPTION
[0043] [1. Acrylic adhesive composition and adhesive layer]
[0044] The acrylic adhesive composition of the present invention is an acrylic adhesive composition for forming an adhesive layer used for bonding optical components of an image display device, wherein the water contents W1 and W2 of the adhesive layer after applying the following conditions (A) and (B) satisfy the following formula (1).
[0045] W2 / W1>1 …… (1)
[0046] (A) Water content of the adhesive layer after being stored at 23°C and 50% RH for 24 hours: W1 (μg / cm 2 )
[0047] (B) Water content of the adhesive layer after (A) when it was stored at 85°C and 85% RH for 8 hours and then at 23°C and 50% RH for 24 hours: W2 (μg / cm 2 )
[0048] The acrylic adhesive composition of the present invention is used for attaching optical components such as polarizing films, retardation films, optical compensation films, touch sensor films, and cover films to image display panels in image display devices such as liquid crystal displays (LCDs) and organic electroluminescent displays (OLEDs), and touch panels in which touch sensors are incorporated in these image display devices, or for forming an adhesive layer used for attaching these optical components to each other.
[0049] It should be noted that, in this specification, when referring to an "image display device", this also includes a "touch panel" unless otherwise specified.
[0050] In the bonding of the above optical components, an optical component with an adhesive layer having an adhesive sheet attached to the optical component is generally used. When the optical component with an adhesive layer is bonded to a glass substrate, for example, after being placed under high temperature and high humidity conditions such as 85°C and 85%RH and then restored to room temperature, the adhesive layer sometimes becomes white turbid (humidified white turbidity). When humidified white turbidity occurs, it becomes a cause of reduced visual recognition of the image display device.
[0051] It is believed that the reason why the adhesive layer generates humidified white turbidity when the adhesive layer returns to normal temperature after high temperature humidification is that the water absorbed by the adhesive layer under high temperature humidification is released from the adhesive layer and condensed when the adhesive layer returns to normal temperature, thereby generating white turbidity. Therefore, it is believed that the water contents W1 and W2 after the above-mentioned conditions (A) and (B) are applied to the above-mentioned adhesive layer satisfy the above-mentioned formula (1), that is, the water content W2 is greater than the water content W1. Such a structure can suppress the amount of water released and condensed from the adhesive layer when the adhesive layer returns to normal temperature from the high temperature humidification condition, thereby not easily generating humidified white turbidity, and can maintain the visual recognition of the image display device.
[0052] From the viewpoint of suppressing the amount of water released and condensed from the adhesive layer when returning to normal temperature from high temperature and humidification conditions, and further suppressing humidification white turbidity, the above W2 / W1 is preferably 1.05 or more, more preferably 1.1 or more, and further preferably 1.15 or more. The upper limit of the above W2 / W1 is not particularly limited and can be 2 or less.
[0053] In the acrylic pressure-sensitive adhesive composition of the present invention, the water contents W1 and W3 after the pressure-sensitive adhesive layer is subjected to the following conditions (A) and (C) preferably satisfy the following formula (2).
[0054] W3 / W1>2.3 …… (2)
[0055] (A) Water content of the adhesive layer after being stored at 23°C and 50% RH for 24 hours: W1 (μg / cm 2 )
[0056] (C) Water content of the adhesive layer after (A) after being stored at 85°C and 85% RH for 8 hours: W3 (μg / cm 2 )
[0057] The above-mentioned W3 / W1 satisfies the above-mentioned formula (2), that is, the above-mentioned W3 / W1 is greater than 2.3. Such a structure is preferred from the following viewpoints: the more moisture the adhesive layer absorbs under high temperature and high humidity conditions, the easier it is for the adhesive layer to retain moisture, and then when it returns to normal temperature, the amount of moisture released and condensed from the adhesive layer becomes less, that is, the above-mentioned W2 / W1 easily satisfies the above-mentioned formula (1), and even if it is placed under high temperature and high humidity conditions and then returned to normal temperature, it is not easy to produce humidified white turbidity, and the visual recognizability of the image display device can be maintained.
[0058] From the viewpoint that the amount of moisture absorbed by the adhesive layer increases under high temperature and high humidity conditions, and the amount of moisture released and condensed from the adhesive layer decreases when the temperature returns to normal, and the humidification white turbidity can be further suppressed, the above W3 / W1 is preferably 2.35 or more, more preferably 2.4 or more, further preferably 2.45 or more, and may also be 2.5 or more. The upper limit of the above W3 / W1 is not particularly limited, and may be 5 or less.
[0059] In the acrylic adhesive composition of the present invention, the water content W1 (μg / cm 2 ) is not particularly limited, but is preferably 117 μg / cm , from the viewpoint that the amount of moisture absorbed by the adhesive layer under high temperature and high humidity conditions increases, and the amount of moisture released and condensed from the adhesive layer when it returns to room temperature decreases, which can further suppress humidification white turbidity. 2 More preferably, 118 μg / cm 2 More preferably, 119 μg / cm 2 Above, 120 μg / cm 2 The above water content W1 (μg / cm 2 ) has no particular upper limit and can be 1000 μg / cm 2 the following.
[0060] In the acrylic adhesive composition of the present invention, the water content W2 (μg / cm 2 ) is not particularly limited, but is preferably 120 μg / cm , from the viewpoint that the amount of moisture absorbed by the adhesive layer under high temperature and high humidity conditions increases, and the amount of moisture released and condensed from the adhesive layer decreases when the temperature returns to normal, and that humidification white turbidity can be further suppressed. 2 More preferably, 130 μg / cm 2More preferably, 135 μg / cm 2 Above, it can also be 140μg / cm 2 The above water content W2 (μg / cm 2 ) has no particular upper limit and can be 2000 μg / cm 2 the following.
[0061] In the acrylic adhesive composition of the present invention, the water content W3 (μg / cm 2 ) is not particularly limited, but is preferably 280 μg / cm , from the viewpoint that the amount of water absorbed by the adhesive layer under high temperature and high humidity conditions increases, and the amount of water released and condensed from the adhesive layer when it returns to room temperature decreases, which can further suppress humidification white turbidity. 2 More preferably, 290 μg / cm 2 More preferably, 300 μg / cm 2 Above, it can also be 310μg / cm 2 The above water content W3 (μg / cm 2 ) has no particular upper limit and can be 5000 μg / cm 2 the following.
[0062] In the acrylic adhesive composition of the present invention, specifically, the above-mentioned water contents W1, W2, W3, and their ratios W2 / W1 and W3 / W1 are measured by the water content measurement in the examples described later, and can be adjusted by, for example, the monomer composition of the acrylic polymer described later (the type, content, composition, etc. of the functional group-containing monomer), the type or amount of the cross-linking agent, the type or amount of the hydrogenated polyolefin resin, etc.
[0063] For the adhesive layer of the present invention, from the viewpoint of preventing malfunction of the touch panel having the adhesive layer, the dielectric constant is preferably controlled to be low, but there is no particular restriction. The dielectric constant of the adhesive layer of the present invention at a frequency of 100kHz is preferably 4 or less, more preferably 3.9 or less, and further preferably 3.8 or less. The lower limit of the dielectric constant at a frequency of 100kHz is not particularly limited, but is preferably 2.3 or more, more preferably 2.4 or more, and further preferably 2.5 or more.
[0064] Specifically, the dielectric constant of the adhesive layer of the present invention is measured by the dielectric constant measurement in the examples described below, and can be adjusted by, for example, the monomer composition of the acrylic polymer described below (the type, content, composition, etc. of the functional group-containing monomer), the type or amount of the cross-linking agent, the type or amount of the hydrogenated polyolefin resin, etc.
[0065] The pressure-sensitive adhesive layer of the present invention or the pressure-sensitive adhesive sheet of the present invention described below is used to bond optical members of an image display device and therefore has excellent transparency. Therefore, the visibility and appearance of the pressure-sensitive adhesive layer or pressure-sensitive adhesive sheet of the present invention are excellent.
[0066] The haze of the adhesive layer or adhesive sheet of the present invention (according to JIS K7136) is not particularly limited, preferably 1.0% or less, more preferably 0.8% or less. When the haze is 1.0% or less, excellent transparency and excellent appearance can be obtained, which is preferred. The lower limit of the haze is not particularly limited, and is theoretically 0%, and can be greater than 0.01% in actual use. It should be noted that the above haze can be measured, for example, as follows: an adhesive layer (thickness: 100 μm) or an adhesive sheet containing the adhesive layer is made, and it is left to stand for at least 24 hours under normal conditions (23°C, 50% RH), and then attached to a slide glass (for example, a slide glass with a total transmittance of 92% and a haze of 0.2%), and it is used as a sample, and a haze meter (manufactured by Murakami Color Technology Research Institute Co., Ltd., trade name "HM-150N") or its equivalent is used for measurement.
[0067] The total light transmittance (according to JIS K7361-1) in the visible light wavelength range of the adhesive layer or adhesive sheet of the present invention is not particularly limited, preferably 90% or more, more preferably 91% or more, and further preferably 92% or more. When the total light transmittance is 90% or more, excellent transparency and excellent appearance can be obtained, which is preferred. The upper limit of the total light transmittance is not particularly limited, and in theory, it is a value obtained by deducting the light loss (Fresnel loss) caused by the reflection generated at the air interface from 100%, and in actual use, it can be 95% or less. It should be noted that the above-mentioned total light transmittance can be measured, for example, as follows: an adhesive layer (thickness: 100 μm) or an adhesive sheet containing the adhesive layer is prepared, and it is allowed to stand at a normal temperature (23° C., 50% RH) for at least 24 hours, and then the release liner is peeled off in the case of a release liner, and the adhesive layer or the adhesive sheet containing the adhesive layer is attached to a slide glass (for example, a slide glass with a total light transmittance of 92% and a haze of 0.2%), and it is used as a sample and measured using a haze meter (manufactured by Murakami Color Technology Laboratory Co., Ltd., trade name "HM-150N") or its equivalent.
[0068] The thickness of the adhesive layer of the present invention is not particularly limited, and is preferably 12 μm to 350 μm, and more preferably 12 μm to 300 μm. When the thickness is above a certain value, it is preferred from the perspective of being able to fully relax the stress with the metal wiring and prevent uneven display in a touch panel bonded with an optical component (touch sensor film) having metal wiring such as a metal mesh film and a silver nanowire film. In addition, when the thickness is below a certain value, operability and manufacturability are particularly excellent, which is preferred.
[0069] The method for preparing the adhesive layer of the present invention is not particularly limited, and may be, for example, preparing the acrylic adhesive composition (precursor composition) of the present invention, coating (applying) it on a substrate or a release liner, and irradiating with active energy rays, heating and drying, etc. as required.
[0070] It should be noted that the adhesive composition can be applied by a known coating method, for example, a coating machine such as a gravure roll coater, a reverse roll coater, a lick coater, a dip roll coater, a bar coater, a knife coater, a spray coater, a comma coater, or a direct coater can be used.
[0071] The acrylic adhesive composition of the present invention may have any form, for example, an emulsion type, a hot melt type (hot melt type), a solvent-free type (active energy ray curing type, such as a monomer mixture, or a monomer mixture and a partial polymer thereof, etc.). In particular, the acrylic adhesive composition of the present invention is preferably not a solvent type. This is because, when an adhesive layer is to be obtained using a solvent-type adhesive composition, poor appearance such as orange peel wrinkles is likely to occur. It should be noted that "orange peel wrinkles" refers to the phenomenon of producing bumps like the skin of "grapefruit", a type of citrus fruit. In addition, from the perspective of obtaining an adhesive layer with excellent appearance, the acrylic adhesive composition of the present invention is preferably an active energy ray curing type. In this specification, an adhesive composition refers to a composition for forming an adhesive layer, including the meaning of a composition for forming an adhesive.
[0072] As described above, the acrylic pressure-sensitive adhesive composition of the present invention is preferably not a solvent-based composition, that is, preferably contains no or substantially no organic solvent.
[0073] As the above-mentioned organic solvent, there is no particular limitation as long as it is an organic compound used as a solvent, and examples thereof include: hydrocarbon solvents such as cyclohexane, hexane, and heptane; aromatic solvents such as toluene and xylene; ester solvents such as ethyl acetate and methyl acetate; ketone solvents such as acetone and methyl ethyl ketone; alcohol solvents such as methanol, ethanol, butanol, and isopropanol, etc. It should be noted that the above-mentioned organic solvent may be a mixed solvent containing two or more organic solvents.
[0074] In the acrylic adhesive composition of the present invention, "substantially containing no organic solvent" means that no organic solvent is actively mixed except when the organic solvent is inevitably mixed in. Specifically, the content of the organic solvent in the adhesive composition is 1.0 wt % or less (preferably 0.5 wt % or less, more preferably 0.2 wt % or less) relative to the total amount of the adhesive composition (total weight, 100 wt %), and it can be said that the adhesive composition does not contain substantially any organic solvent.
[0075] The acrylic adhesive composition of the present invention preferably has a halogen ion concentration of 50 ppm or less. This configuration is preferred from the viewpoint of being able to obtain an anti-corrosion effect on metal wiring in a touch panel bonded with an optical component (touch sensor film) having metal wiring such as a metal mesh film and a silver nanowire film. Relative to the total amount of the above-mentioned adhesive composition, the content of halogen ions is preferably 50 ppm or less (e.g., 0 to 50 ppm), more preferably 40 ppm or less (e.g., 0 to 40 ppm), and further preferably 30 ppm or less (e.g., 0 to 30 ppm), and it can be said that it is substantially free of halogen ions.
[0076] The acrylic adhesive composition of the present invention preferably does not contain or substantially does not contain a carboxyl group-containing monomer as a monomer component constituting the acrylic polymer. Therefore, in a touch panel to which an optical component (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is attached, an anti-corrosion effect on the metal wiring can be obtained. The content of the carboxyl group-containing monomer is preferably 1 ng / cm 2 Below (e.g. 0-1 ng / cm 2 ), more preferably 0.8 ng / cm 2 Below (e.g. 0 to 0.8 ng / cm 2 ), more preferably 0.5 ng / cm 2 Below (e.g. 0 to 0.5 ng / cm 2 ) can be said to be substantially free of. It should be noted that, as the above-mentioned carboxyl group-containing monomer, for example, (meth) acrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, etc. can be cited, and in addition, the above-mentioned carboxyl group-containing monomer also includes anhydride group-containing monomers such as maleic anhydride and itaconic anhydride.
[0077] Specifically, the halogen ion content and the carboxyl group-containing monomer content of the acrylic adhesive composition of the present invention can be measured by the method for measuring the halogen ion content and the acrylate ion content in the examples described later, and can be adjusted by, for example, the monomer composition of the acrylic polymer described later (the type, content, composition, etc. of the functional group-containing monomer), the type or amount of the cross-linking agent, the type or amount of the hydrogenated polyolefin resin, etc.
[0078] [1-1. Acrylic polymer]
[0079] The acrylic pressure-sensitive adhesive composition of the present invention is a pressure-sensitive adhesive composition containing an acrylic polymer as a base polymer. The acrylic polymer may be used alone or in combination of two or more.
[0080] The acrylic pressure-sensitive adhesive composition of the present invention may contain, in addition to the acrylic polymer, a hydrogenated polyolefin resin, a polyfunctional (meth)acrylate, a silane coupling agent, and other additives as described below.
[0081] The content of the acrylic polymer is not particularly limited, but is preferably 60 wt % or more (e.g., 60 wt % to 99.9 wt %), and more preferably 70 wt % or more (e.g., 70 wt % to 99.9 wt %), relative to the total weight (total weight, 100 wt %) of the acrylic pressure-sensitive adhesive composition of the present invention.
[0082] The acrylic adhesive composition of the present invention for forming an adhesive layer containing an acrylic polymer as a main component is not particularly limited, and examples thereof include: a composition containing an acrylic polymer as an essential component; a composition containing a mixture of monomer components constituting an acrylic polymer (sometimes referred to as a "monomer mixture") or a partial polymer thereof as an essential component, etc. As the former, for example, so-called water-dispersible compositions (emulsion compositions) etc. can be listed, and as the latter, for example, so-called active energy ray-curable compositions etc. can be listed, but there are no particular limitations. Among them, the acrylic adhesive composition of the present invention is preferably a composition containing a monomer mixture or a partial polymer thereof as an essential component.
[0083] In this specification, the above-mentioned "mixture of monomer components" includes the case where it is composed of a single monomer component and the case where it is composed of two or more monomer components. In addition, the above-mentioned "partial polymer of a mixture of monomer components" refers to a composition in which one or more monomer components among the monomer components constituting the above-mentioned "mixture of monomer components" are partially polymerized.
[0084] In this specification, the term "acrylic polymer" includes "acrylic polymer", "mixture of monomer components constituting acrylic polymer" and "partial polymer of the mixture of monomer components constituting acrylic polymer" unless otherwise specified.
[0085] An acrylic polymer is a polymer (polymer) containing an acrylic monomer (acrylic monomer) as an essential monomer unit (monomer unit, monomer structural unit). In other words, an acrylic polymer is a polymer containing a structural unit derived from an acrylic monomer as a structural unit. That is, an acrylic polymer is a polymer constituted (formed) with an acrylic monomer as an essential monomer component. It should be noted that in this specification, "(meth)acrylic acid" means either or both of "acrylic acid" and "methacrylic acid", and the same applies to the others. The weight average molecular weight of the acrylic polymer is not particularly limited, and is preferably 100,000 to 5,000,000.
[0086] As a preferred first embodiment of the acrylic pressure-sensitive adhesive composition of the present invention, the acrylic polymer is preferably a polymer containing, as monomer units, an alkyl (meth)acrylate having a linear or branched alkyl group (hereinafter sometimes simply referred to as "alkyl (meth)acrylate") and an alicyclic structure-containing monomer.
[0087] In the first embodiment, examples of the alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate (n-butyl (meth)acrylate), isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, and tert-butyl (meth)acrylate. (meth)acrylate, wherein the alkyl group has 1 to 24 carbon atoms, such as nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, etc. It should be noted that the alkyl (meth)acrylate may be used alone or in combination of two or more.
[0088] In the first embodiment, as the alkyl (meth)acrylate, alkyl acrylate is preferred over alkyl methacrylate in that the polymerization time of the acrylic polymer can be shortened to improve productivity. In particular, when the acrylic polymer of the present invention is cured by radiation polymerization, alkyl acrylate is preferred.
[0089] Among the above-mentioned alkyl (meth)acrylates, from the viewpoint of obtaining strong adhesiveness and adjusting residual stress, alkyl (meth)acrylates having an alkyl group with 1 to 18 carbon atoms are preferred, methyl methacrylate (MMA), butyl acrylate (BA), 2-ethylhexyl acrylate (2EHA), and isostearyl acrylate (ISTA) are more preferred, and butyl acrylate (BA) is more preferred.
[0090] The content (ratio) of the alkyl (meth)acrylate in all monomer units of the acrylic polymer in the first embodiment (the total amount of monomer components constituting the acrylic polymer) is not particularly limited. From the viewpoint of improving durability and obtaining high adhesive reliability, the content (ratio) of the alkyl (meth)acrylate is preferably 30 to 90 parts by weight, more preferably 35 to 85 parts by weight, and even more preferably 40 to 80 parts by weight, relative to the total amount (100 parts by weight) of the monomer components constituting the acrylic polymer.
[0091] It should be noted that, in this specification, the term "the total amount of monomer components constituting the acrylic polymer" also includes monomer components added to the acrylic adhesive composition containing the acrylic polymer for the purpose of adjusting the elastic modulus of the adhesive layer in the acrylic adhesive composition of the present invention.
[0092] The alicyclic structure-containing monomer in the first embodiment refers to a monomer having a polymerizable functional group having an unsaturated double bond such as a (meth)acryloyl group or a vinyl group and having an alicyclic structure. For example, an alkyl (meth)acrylate having a cycloalkyl group is included in the above-mentioned alicyclic structure-containing monomer. However, a monomer having at least one alicyclic structure in the molecule and at least one carboxyl group in the molecule is a carboxyl-containing monomer, not an alicyclic structure-containing monomer. It should be noted that the alicyclic structure-containing monomer can be used alone or in combination of two or more.
[0093] The alicyclic structure in the alicyclic structure-containing monomer is a cyclic hydrocarbon structure, and preferably has 5 or more carbon atoms, more preferably 6 to 24 carbon atoms, further preferably 6 to 15 carbon atoms, and particularly preferably 6 to 10 carbon atoms.
[0094] Examples of the alicyclic structure-containing monomer include (meth)acrylic acid cyclopropyl, (meth)acrylic acid cyclobutyl, (meth)acrylic acid cyclopentyl, (meth)acrylic acid cyclohexyl, (meth)acrylic acid 3,3,5-trimethylcyclohexyl, (meth)acrylic acid cycloheptyl, (meth)acrylic acid cyclooctyl, (meth)acrylic acid isobornyl, (meth)acrylic acid tetrahydrodicyclopentadienyl, HPMPA represented by the following formula (1), TMA-2 represented by the following formula (2), and HCPA represented by the following formula (3). It should be noted that in the following formula (3), there is no particular limitation on the bonding position of the cyclohexyl ring connected by a line to the structural formula in the brackets. Among them, isobornyl, (meth)acrylic acid cyclohexyl, and (meth)acrylic acid 3,3,5-trimethylcyclohexyl are preferred.
[0095]
[0096]
[0097]
[0098] Among them, from the viewpoint of obtaining durability and strong adhesiveness, the alicyclic structure-containing monomer is preferably cyclohexyl acrylate (CHA).
[0099] The content (ratio) of the above-mentioned alicyclic structure-containing monomer in all monomer units of the acrylic polymer in the first embodiment (the total amount of monomer components constituting the acrylic polymer) is not particularly limited. From the perspective of improving durability and adhesive reliability, the content (ratio) of the above-mentioned alicyclic structure-containing monomer is preferably 3 parts by weight to 50 parts by weight, more preferably 5 parts by weight to 40 parts by weight, and even more preferably 10 parts by weight to 30 parts by weight, relative to the total amount of monomer components constituting the acrylic polymer (100 parts by weight).
[0100] The total content (ratio) of the alkyl (meth)acrylate and the alicyclic structure-containing monomer in all monomer units (the total amount of monomer components constituting the acrylic polymer) of the acrylic polymer in the first embodiment is not particularly limited. From the perspective of improving durability and adhesive reliability, the total content (ratio) of the alkyl (meth)acrylate and the alicyclic structure-containing monomer is preferably 40 to 95 parts by weight, more preferably 50 to 90 parts by weight, and even more preferably 60 to 85 parts by weight, relative to the total amount (100 parts by weight) of the monomer components constituting the acrylic polymer.
[0101] The weight ratio of the alkyl (meth)acrylate to the alicyclic structure-containing monomer in the acrylic polymer of the first embodiment (alkyl (meth)acrylate / alicyclic structure-containing monomer) is not particularly limited, but is preferably 5 / 95 to 95 / 5, more preferably 10 / 90 to 90 / 10, and still more preferably 15 / 85 to 85 / 15 from the perspective of improving durability and adhesive reliability.
[0102] As a preferred second embodiment of the acrylic adhesive composition of the present invention, the acrylic polymer is preferably a polymer containing an alkyl (meth)acrylate having an alkyl group having 8 or more carbon atoms (sometimes referred to as "alkyl (meth)acrylate (A)") as an essential monomer unit. That is, the acrylic polymer of the second embodiment is preferably obtained by polymerizing a monomer component containing an alkyl (meth)acrylate having a medium-chain to long-chain alkyl group such as alkyl (meth)acrylate (A). The acrylic polymer can realize a highly flexible adhesive layer through the action of the above-mentioned medium-chain to long-chain alkyl group, and even when an optical component (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is bonded, the stress with the metal wiring can be fully relaxed, thereby preventing display unevenness, which is preferred in this regard.
[0103] In the second embodiment, examples of the alkyl (meth)acrylate (A) include alkyl (meth)acrylates having an alkyl group with 8 or more carbon atoms (preferably 8 to 24 carbon atoms) such as octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. The alkyl (meth)acrylate (A) may be used alone or in combination of two or more.
[0104] In the second embodiment, as the alkyl (meth)acrylate (A), an alkyl acrylate is preferred over an alkyl methacrylate in that the polymerization time of the acrylic polymer (A) can be shortened to improve productivity. In particular, when the acrylic polymer of the present invention is cured by radiation polymerization, an alkyl acrylate is preferred.
[0105] Among them, as the (meth) acrylate alkyl ester (A), from the perspective of being able to realize a highly flexible adhesive layer and being able to fully relax the stress with the metal wiring even when laminating an optical component (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film, thereby preventing uneven display, it is preferred to include a (meth) acrylate alkyl ester having a branched alkyl group with 8 or more carbon atoms, preferably an (meth) acrylate alkyl ester having a branched alkyl group with 8 or 9 carbon atoms, further preferably 2-ethylhexyl (meth) acrylate, and particularly preferably 2-ethylhexyl acrylate (2EHA). The number of carbon atoms of the side chain alkyl group of the above-mentioned branched alkyl group is not particularly limited, and an alkyl group having 1 to 3 carbon atoms (such as methyl, ethyl, n-propyl, isopropyl) is preferred. "Side chain alkyl" is an alkyl group substituted on the side chain of the carbon chain with the largest number of carbon atoms.
[0106] In the second embodiment, the content (ratio) of the alkyl (meth)acrylate (A) in all monomer units of the acrylic polymer (the total amount of monomer components constituting the acrylic polymer) is not particularly limited. However, from the perspective of achieving a highly flexible adhesive layer and being able to sufficiently relax the stress on the metal wiring even when an optical member (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is bonded to prevent display unevenness, the content (ratio) of the alkyl (meth)acrylate (A) is preferably 30 to 99 parts by weight, more preferably 35 to 95 parts by weight, and even more preferably 40 to 90 parts by weight relative to the total amount (100 parts by weight) of the monomer components constituting the acrylic polymer.
[0107] In the second embodiment, when the alkyl (meth)acrylate (A) includes an alkyl (meth)acrylate having a branched alkyl group having 8 or 9 carbon atoms (hereinafter, in this specification, sometimes referred to as an alkyl (meth)acrylate (A1)), it is preferred that the alkyl (meth)acrylate (A) further includes an alkyl (meth)acrylate having a branched alkyl group having 10 to 24 carbon atoms (hereinafter, in this specification, sometimes referred to as an alkyl (meth)acrylate (A2)).
[0108] In the second embodiment, when the alkyl (meth)acrylate (A) contains an alkyl (meth)acrylate (A2) in addition to the alkyl (meth)acrylate (A1), the dielectric constant of the adhesive layer of the present invention can be reduced by the action of the long-chain branched alkyl group. Even when the adhesive layer is attached to an optical member (touch sensor film) having a metal wiring layer such as a metal mesh wiring or silver nanowire, the adhesive layer has a low dielectric constant, and thus erroneous operation can be prevented. This is preferred.
[0109] The Tg of the homopolymer of the (meth) alkyl acrylate (A2) is preferably -80°C to 0°C, and more preferably -70°C to -10°C. When the Tg of the homopolymer is below -80°C, the elastic modulus of the adhesive layer at room temperature is sometimes excessively reduced, which is not preferred. When the Tg of the homopolymer is greater than 0°C, the adhesive force is sometimes reduced, which is not preferred. The Tg of the homopolymer is a value measured by a differential scanning calorimeter (DSC). In addition, from the perspective of being able to satisfy a moderate low dielectric constant and elastic modulus, although the branched alkyl group having 10 to 24 carbon atoms has 10 to 24 carbon atoms, the (meth) alkyl acrylate having a preferred alkyl group can be appropriately selected according to the method for producing the (meth) acrylic polymer. For example, in the case of producing a (meth) acrylic polymer by solution polymerization, the above-mentioned alkyl group is more preferably 10 to 18 carbon atoms, more preferably 10 to 16 carbon atoms, and more preferably 10 to 14 carbon atoms. When the acrylic polymer is produced by radiation polymerization or the like, the alkyl group preferably has 12 to 18 carbon atoms, and more preferably has 14 to 18 carbon atoms.
[0110] Examples of the (meth)acrylic acid alkyl ester (A2) include isodecyl acrylate (having 10 carbon atoms, Tg of the homopolymer = -60°C, hereinafter referred to as Tg), isodecyl methacrylate (having 10 carbon atoms, Tg = -41°C), isomyristyl acrylate (having 14 carbon atoms, Tg = -56°C), isostearyl acrylate (having 18 carbon atoms, Tg = -18°C), 2-propylheptyl acrylate, isondecyl acrylate, isododecyl acrylate, isotridecyl acrylate, isopentadecyl acrylate, isohexadecyl acrylate, isoheptadecyl acrylate, and the methacrylic acid ester monomers exemplified above. The (meth)acrylic acid alkyl ester (A2) may be used alone or in combination of two or more.
[0111] In addition, among the branched alkyl groups having 10 to 24 carbon atoms, groups having a branched alkyl group such as a tert-butyl group at the end of the ester group are particularly preferred in the following aspects: the molar volume increases and the dipole moment decreases, and it is believed that an adhesive layer having a balance between the two can be obtained. As the branched alkyl group at the end of the ester group, a branched alkyl group having 4 to 6 carbon atoms such as a tert-butyl group, a neopentyl group, and a tert-amyl group is preferred, and a tert-butyl group is particularly preferred. As a preferred example of the (meth)acrylic acid alkyl ester (A2) having a tert-butyl group at the end of the ester group, isostearyl acrylate represented by the following formula can be cited.
[0112]
[0113] In the second embodiment, the content (ratio) of the above-mentioned (meth) alkyl acrylate (A1) in all monomer units of the acrylic polymer (the total amount of monomer components constituting the acrylic polymer) is not particularly limited. From the perspective of being able to realize a highly flexible adhesive layer and being able to fully relax the stress with the metal wiring even when an optical component (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is attached, thereby preventing uneven display, the content (ratio) of the above-mentioned (meth) alkyl acrylate (A1) is preferably 30 parts by weight or more, more preferably 35 parts by weight or more, further preferably 40 parts by weight or more, and may also be 45 parts by weight or more, relative to the total amount of monomer components constituting the acrylic polymer (100 parts by weight). In addition, from the perspective of reducing the dielectric constant of the adhesive layer to prevent erroneous operation, the above-mentioned content is preferably 70 parts by weight or less, more preferably 65 parts by weight or less, and further preferably 60 parts by weight or less.
[0114] In the second embodiment, the content (ratio) of the above-mentioned (meth) alkyl acrylate (A2) in all monomer units of the acrylic polymer (total amount of monomer components constituting the acrylic polymer is 100 parts by weight) is not particularly limited. From the viewpoint of reducing the dielectric constant of the adhesive layer to prevent erroneous operation, it is preferably 10 parts by weight or more, more preferably 15 parts by weight or more, and further preferably 20 parts by weight or more. In addition, from the viewpoint of being able to realize a highly flexible adhesive layer and being able to fully relax the stress with the metal wiring even when an optical member (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is attached to prevent uneven display, the above-mentioned content is preferably 50 parts by weight or less, more preferably 40 parts by weight or less, further preferably 35 parts by weight or less, and particularly preferably 30 parts by weight or less.
[0115] The weight ratio of the above-mentioned (meth) alkyl acrylate (A1) and (meth) alkyl acrylate (A2) in the acrylic polymer of the second embodiment ((meth) alkyl acrylate (A2) / (meth) alkyl acrylate (A1)) is not particularly limited. From the perspective of being able to achieve a highly flexible adhesive layer and being able to fully relax the stress with the metal wiring even when an optical component (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is bonded to prevent uneven display, it is preferably 1.1 or less, more preferably 0.6 or less, further preferably 0.55 or less, particularly preferably 0.5 or less, and may also be 0.45 or less. In addition. From the perspective of reducing the dielectric constant of the adhesive layer to prevent erroneous operation, the above ratio is preferably 0.2 or more, more preferably 0.25 or more, further preferably 0.3 or more, and may also be 0.35 or more.
[0116] In the second embodiment, the acrylic polymer may contain an alkyl (meth)acrylate other than the alkyl (meth)acrylate (A) (hereinafter sometimes referred to as "alkyl (meth)acrylate (B)") as a monomer component. Examples of the alkyl (meth)acrylate (B) include alkyl (meth)acrylates having a linear or branched alkyl group having 1 to 7 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate (n-butyl (meth)acrylate), isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, amyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, and heptyl (meth)acrylate. The alkyl (meth)acrylate (B) may be used alone or in combination of two or more.
[0117] In the second embodiment, the content (ratio) of the alkyl (meth)acrylate (B) in all monomer units of the acrylic polymer (the total amount of monomer components constituting the acrylic polymer) is not particularly limited. However, from the perspectives of achieving a highly flexible adhesive layer and being able to sufficiently relax the stress on the metal wiring even when an optical member (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is bonded to prevent display unevenness, the content (ratio) of the alkyl (meth)acrylate (B) is preferably 10 parts by weight or less, and more preferably 5 parts by weight or less, relative to the total amount (100 parts by weight) of the monomer components constituting the acrylic polymer.
[0118] In the acrylic adhesive composition of the present invention (the acrylic adhesive composition of the first embodiment and the second embodiment), the acrylic polymer may contain a copolymerizable functional group-containing monomer (copolymerizable functional group-containing monomer) as a monomer unit in addition to the above-mentioned (meth) alkyl acrylate (including (meth) alkyl acrylate (A) and (meth) alkyl acrylate (B)) and alicyclic structure-containing monomer. That is, the acrylic polymer may contain a functional group-containing monomer as a monomer component. It should be noted that the functional group-containing monomer may be used alone or in combination of two or more.
[0119] The content (ratio) of the functional group-containing monomer relative to the total amount of monomer components constituting the acrylic polymer (100 parts by weight) is not particularly limited, but is preferably 10 parts by weight to 40 parts by weight, more preferably 15 parts by weight to 37 parts by weight, and even more preferably 20 parts by weight to 35 parts by weight, from the viewpoint of suppressing the amount of water released and condensed from the adhesive layer when returning to room temperature from high-temperature humidification conditions, thereby less likely to produce humidified white turbidity and maintaining the visual recognizability of the image display device.
[0120] From the viewpoint of suppressing the amount of water released and condensed from the adhesive layer when returning from high temperature and humidification conditions to room temperature, thereby not easily generating humidified white turbidity and maintaining the visual recognizability of the image display device, the acrylic polymer preferably contains only one kind of functional group-containing monomer as a monomer unit. In the case where the acrylic polymer contains only one kind of functional group-containing monomer as a monomer unit, from the viewpoint of suppressing the amount of water released and condensed from the adhesive layer when returning from high temperature and humidification conditions to room temperature, thereby not easily generating humidified white turbidity and maintaining the visual recognizability of the image display device, the content (ratio) of the functional group-containing monomer is preferably 20 to 40 parts by weight, more preferably 25 to 37 parts by weight, and further preferably 30 to 35 parts by weight relative to the total amount of monomer components constituting the acrylic polymer (100 parts by weight).
[0121] In the case where the acrylic polymer contains two or more functional group-containing monomers as monomer units, from the viewpoint of suppressing the amount of water released and condensed from the adhesive layer when returning to room temperature from high temperature and humidification conditions, thereby being less likely to produce humidified white turbidity and maintaining the visual recognizability of the image display device, the content (ratio) of the highest functional group-containing monomer is preferably 75 parts by weight or more, more preferably 80 parts by weight or more, and even more preferably 85 parts by weight or more, relative to the total amount (100 parts by weight) of the functional group-containing monomer components constituting the acrylic polymer.
[0122] As the above-mentioned functional group-containing monomer, preferably, a hydroxyl-containing monomer can be cited. When the acrylic polymer contains a hydroxyl-containing monomer as a monomer unit, the amount of moisture absorbed by the adhesive layer under high temperature and high humidity conditions increases, and then the moisture released and condensed from the adhesive layer when it returns to room temperature decreases, which can further suppress humidification white turbidity. In addition, when the monomer components constituting the polymerization are polymerized, it is easy to polymerize, and it is easy to obtain good cohesive force. Therefore, it is easy to obtain strong adhesiveness and excellent foaming and peeling resistance. In addition, it is easy to suppress the whitening of the adhesive sheet that sometimes occurs under high humidity environments.
[0123] In the case where the acrylic polymer contains the hydroxyl-containing monomer as the functional group-containing monomer component constituting the polymer with the largest content, from the viewpoint that the amount of moisture absorbed by the adhesive layer increases under high temperature and high humidity conditions, and the moisture released and condensed from the adhesive layer decreases when it returns to room temperature, and the humidification white turbidity can be further suppressed, the content (ratio) of the hydroxyl-containing monomer is preferably 20 parts by weight or more, more preferably 25 parts by weight or more, and further preferably 30 parts by weight or more relative to the total amount of monomer components constituting the acrylic polymer (100 parts by weight). In addition, the upper limit of the content of the hydroxyl-containing monomer is not particularly limited, and is preferably 40 parts by weight or less, more preferably 37 parts by weight or less, and further preferably 35 parts by weight or less.
[0124] In addition, as the above-mentioned functional group-containing monomer, preferably, nitrogen-containing monomers can be cited. When the acrylic polymer contains a nitrogen-containing monomer as a monomer unit, the amount of moisture absorbed by the adhesive layer increases under high temperature and high humidity conditions, and then the moisture released and condensed from the adhesive layer when it returns to room temperature decreases, which can further suppress humidification white turbidity. In addition, it is easy to obtain moderate cohesion, so the 180° (degree) peeling adhesive force to the glass plate and the 180° peeling adhesive force to the acrylic polymer plate are increased, and strong adhesion is easy to obtain, and excellent foaming resistance and peeling property are easy to obtain. In addition, the adhesive layer is easy to obtain moderate flexibility, and the 300% tensile residual stress is adjusted to a specific range. Even in the case of laminating an optical component (touch sensor film) with metal wiring such as a metal mesh film and a silver nanowire film, the stress with the metal wiring can be fully relaxed, thereby preventing uneven display.
[0125] In the case where the acrylic polymer contains the nitrogen-atom-containing monomer as the functional group-containing monomer component constituting the polymer with the largest content, the proportion of the nitrogen-atom-containing monomer in all monomer components (100 parts by weight) constituting the acrylic polymer is not particularly limited, and is preferably 16 parts by weight or more, more preferably 18 parts by weight or more, and further preferably 20 parts by weight or more. When the above ratio is 16 parts by weight or more, it is preferred from the viewpoint that the amount of moisture absorbed by the adhesive layer under high temperature and high humidity conditions increases, and then the amount of moisture released and condensed from the adhesive layer when it returns to room temperature decreases, and the humidification white turbidity can be further suppressed. In addition, it is preferred from the viewpoint that good cohesion is easily obtained and adhesion reliability at high temperature is easily obtained. In addition, it is preferred that the suppression and durability of white turbidity under high humidity environments can be further improved, and higher adhesion reliability to metal mesh wiring or silver nanowire layers can be obtained. In addition, from the perspective of obtaining an adhesive layer with moderate softness to prevent display unevenness and obtaining an adhesive layer with excellent transparency, the upper limit of the proportion of the above-mentioned nitrogen atom-containing monomer is preferably 40 parts by weight or less, more preferably 35 parts by weight or less, and further preferably 30 parts by weight or less.
[0126] In the case where the acrylic polymer contains a hydroxyl-containing monomer and a nitrogen atom-containing monomer as the functional group-containing monomer components constituting the polymer, it is preferred that the content ratio of the functional group-containing monomer having a larger content among the hydroxyl-containing monomer and the nitrogen atom-containing monomer is high, from the viewpoint that the amount of moisture absorbed by the adhesive layer under high temperature and high humidity conditions increases, and the amount of moisture released and condensed from the adhesive layer when returning to room temperature decreases, thereby further suppressing humidification white turbidity.
[0127] In the case where the acrylic polymer contains a hydroxyl-containing monomer and a nitrogen atom-containing monomer as the functional group-containing monomer components constituting the polymer, the content ratio of the functional group-containing monomer having a larger content among the hydroxyl-containing monomer and the nitrogen atom-containing monomer is preferably 75 parts by weight or more, more preferably 80 parts by weight or more, and even more preferably 85 parts by weight or more relative to the total amount (100 parts by weight) of the hydroxyl-containing monomer and the nitrogen atom-containing monomer, from the viewpoint that the amount of moisture absorbed by the adhesive layer under high temperature and high humidity conditions increases, and the amount of moisture released and condensed from the adhesive layer when the temperature is restored to room temperature decreases, thereby further suppressing humidification white turbidity.
[0128] The acrylic polymer can be obtained by polymerizing the monomer units (monomer components) using a known or customary polymerization method. Examples of the polymerization method for the acrylic polymer include a solution polymerization method, an emulsion polymerization method, a bulk polymerization method, and a polymerization method using active energy ray irradiation (active energy ray polymerization method). Among them, from the perspective of transparency, water resistance, cost, etc. of the adhesive layer, the solution polymerization method and the active energy ray polymerization method are preferred, and the active energy ray polymerization method is more preferred.
[0129] As the active energy ray irradiated during the above-mentioned active energy ray polymerization (photopolymerization), for example, ionizing radiation such as α-ray, β-ray, γ-ray, neutron ray, electron ray, etc., ultraviolet rays, etc. are listed, and ultraviolet rays are particularly preferred. In addition, the irradiation energy, irradiation time, irradiation method, etc. of the active energy ray are not particularly limited as long as the photopolymerization initiator can be activated to cause the reaction of the monomer components.
[0130] Various common solvents can be used in the polymerization of the acrylic polymer. Examples of such solvents include esters such as ethyl acetate and n-butyl acetate; aromatic hydrocarbons such as toluene and benzene; aliphatic hydrocarbons such as n-hexane and n-heptane; alicyclic hydrocarbons such as cyclohexane and methylcyclohexane; ketones such as methyl ethyl ketone and methyl isobutyl ketone, and other organic solvents. It should be noted that the solvents can be used alone or in combination of two or more.
[0131] In the polymerization of the acrylic polymer, a polymerization initiator such as a thermal polymerization initiator or a photopolymerization initiator (photoinitiator) may be used depending on the type of polymerization reaction. The polymerization initiator may be used alone or in combination of two or more.
[0132] As the above-mentioned photopolymerization initiator, there is no particular limitation, and examples thereof include: benzoin ether photopolymerization initiators, acetophenone photopolymerization initiators, α-ketol photopolymerization initiators, aromatic sulfonyl chloride photopolymerization initiators, photoactive oxime photopolymerization initiators, benzoin photopolymerization initiators, benzyl photopolymerization initiators, benzophenone photopolymerization initiators, ketal photopolymerization initiators, thioxanthone photopolymerization initiators, etc. It should be noted that the photopolymerization initiator can be used alone or in combination of two or more.
[0133] Examples of the benzoin ether photopolymerization initiator include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-dimethoxy-1,2-diphenylethane-1-one, and anisole methyl ether. Examples of the acetophenone photopolymerization initiator include 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexylphenyl ketone, 4-phenoxydichloroacetophenone, and 4-tert-butyldichloroacetophenone. Examples of the α-ketol photopolymerization initiator include 2-methyl-2-hydroxypropiophenone, 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropane-1-one, and the like. Examples of the aromatic sulfonyl chloride photopolymerization initiator include 2-naphthalenesulfonyl chloride, and the like. Examples of the photoactive oxime-based photopolymerization initiator include 1-phenyl-1,2-propanedione-2-(O-ethoxycarbonyl)oxime. Examples of the benzoin-based photopolymerization initiator include benzoin. Examples of the benzyl-based photopolymerization initiator include benzyl. Examples of the benzophenone-based photopolymerization initiator include benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, α-hydroxycyclohexylphenylketone, and the like. Examples of the ketal-based photopolymerization initiator include benzyldimethylketal, and the like. Examples of the thioxanthone-based photopolymerization initiator include thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone.
[0134] The amount of the photopolymerization initiator used is not particularly limited, and is preferably 0.001 to 1 part by weight, more preferably 0.01 to 0.50 parts by weight, based on 100 parts by weight of all monomer units of the acrylic polymer (the total amount of monomer components constituting the acrylic polymer).
[0135] In addition, as the above-mentioned thermal polymerization initiator, there is no particular limitation, and examples thereof include: azo polymerization initiators, peroxide polymerization initiators (such as dibenzoyl peroxide, tert-butyl permaleate, etc.), redox polymerization initiators, etc. Among them, the azo polymerization initiators disclosed in Japanese Patent Publication No. 2002-69411 are preferred. As the above-mentioned azo polymerization initiators, 2,2'-azobisisobutyronitrile (hereinafter, sometimes referred to as "AIBN"), 2,2'-azobis(2-methylbutyronitrile) (hereinafter, sometimes referred to as "AMBN"), 2,2'-azobis(2-methylpropionic acid) dimethyl ester, 4,4'-azobis(4-cyanovaleric acid), etc. can be mentioned.
[0136] The amount of the thermal polymerization initiator used is not particularly limited. For example, in the case of the azo polymerization initiator, it is preferably 0.05 to 0.5 parts by weight, and more preferably 0.1 to 0.3 parts by weight, relative to 100 parts by weight of all monomer units of the acrylic polymer (the total amount of monomer components constituting the acrylic polymer).
[0137] [1-2. Hydroxyl-containing monomers]
[0138] A hydroxyl-containing monomer refers to a monomer having at least one hydroxyl group in the molecule. In addition, a monomer having at least one hydroxyl group in the molecule and at least one carboxyl group in the molecule is a carboxyl-containing monomer, not a hydroxyl-containing monomer. As the above-mentioned hydroxyl-containing monomer, there is no particular limitation, and specifically, for example, hydroxyl-containing (meth) acrylic acid esters such as 2-hydroxyethyl (meth) acrylate, 2-hydroxypropyl (meth) acrylate, 2-hydroxybutyl (meth) acrylate, 3-hydroxypropyl (meth) acrylate, 4-hydroxybutyl (meth) acrylate, 6-hydroxyhexyl (meth) acrylate, hydroxyoctyl (meth) acrylate, hydroxydecyl (meth) acrylate, hydroxylauryl (meth) acrylate, (meth) acrylate (4-hydroxymethylcyclohexyl) methyl ester, vinyl alcohol, allyl alcohol, etc. Among them, as the above-mentioned hydroxyl-containing monomer, from the viewpoint that the amount of moisture absorbed by the adhesive layer under high temperature and high humidity conditions increases, and then the moisture released and condensed from the adhesive layer when returning to room temperature is reduced, and the humidification white turbidity can be further suppressed; and from the viewpoint that good cohesion and adhesion reliability at high temperature are easily obtained, hydroxyl-containing (meth) acrylates are preferably used, and 2-hydroxyethyl acrylate (HEA), 2-hydroxypropyl acrylate (HPA), 4-hydroxybutyl acrylate (4HBA) are more preferably used. It should be noted that the hydroxyl-containing monomer can be used alone or in combination of two or more.
[0139] [1-3. Nitrogen atom-containing monomers]
[0140] A nitrogen atom-containing monomer refers to a monomer having at least one nitrogen atom in the molecule (in one molecule). However, the above-mentioned hydroxyl-containing monomer does not include the above-mentioned nitrogen atom-containing monomer. That is, in this specification, a monomer having a hydroxyl group and a nitrogen atom in the molecule is included in the nitrogen atom-containing monomer. In addition, a monomer having at least one nitrogen atom in the molecule and at least one carboxyl group in the molecule is a carboxyl-containing monomer, not a nitrogen atom-containing monomer.
[0141] As the nitrogen-containing monomer, N-vinyl cyclic amide, (meth) acrylamide, etc. are preferred from the viewpoint that the amount of moisture absorbed by the adhesive layer under high temperature and high humidity conditions increases, and the moisture released and condensed from the adhesive layer when it returns to room temperature decreases, and the white turbidity caused by humidification can be further suppressed, and the viewpoint of improving the foaming and peeling resistance is considered. It should be noted that the nitrogen-containing monomer can be used alone or in combination of two or more.
[0142] As the above-mentioned N-vinyl cyclic amide, the N-vinyl cyclic amide represented by the following formula (4) is preferred from the viewpoints that the amount of moisture absorbed by the adhesive layer under high temperature and high humidity conditions increases, and the amount of moisture released and condensed from the adhesive layer when the temperature returns to normal temperature decreases, thereby further suppressing humidification white turbidity; and that it is easy to obtain good cohesive force and adhesive reliability at high temperatures.
[0143]
[0144] (In formula (4), R 1 represents a divalent organic group)
[0145] In the above formula (4), R 1 It is a divalent organic group, preferably a divalent saturated hydrocarbon group or an unsaturated hydrocarbon group, and more preferably a divalent saturated hydrocarbon group (for example, an alkylene group having 3 to 5 carbon atoms).
[0146] As the N-vinyl cyclic amide represented by the above formula (4), from the viewpoint of further improving the foaming and peeling resistance, N-vinyl-2-pyrrolidone (NVP), N-vinyl-2-piperidone, N-vinyl-2-caprolactam, N-vinyl-3-morpholinone, N-vinyl-1,3- More preferred are N-vinyl-2-pyrrolidone and N-vinyl-2-caprolactam, and even more preferred is N-vinyl-2-pyrrolidone.
[0147] Examples of the (meth)acrylamides include (meth)acrylamide, N-alkyl (meth)acrylamide, and N,N-dialkyl (meth)acrylamide. Examples of the N-alkyl (meth)acrylamide include N-ethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-n-butyl (meth)acrylamide, and N-octylacrylamide. In addition, the N-alkyl (meth)acrylamide also includes (meth)acrylamide having an amino group, such as dimethylaminoethyl (meth)acrylamide, diethylaminoethyl (meth)acrylamide, and dimethylaminopropyl (meth)acrylamide. Examples of the N,N-dialkyl (meth)acrylamide include N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N,N-dipropyl (meth)acrylamide, N,N-diisopropyl (meth)acrylamide, N,N-di-n-butyl (meth)acrylamide, and N,N-di-tert-butyl (meth)acrylamide.
[0148] In addition, the (meth)acrylamides include, for example, various N-hydroxyalkyl (meth)acrylamides. Examples of the N-hydroxyalkyl (meth)acrylamides include N-methylol (meth)acrylamide, N-(2-hydroxyethyl) (meth)acrylamide, N-(2-hydroxypropyl) (meth)acrylamide, N-(1-hydroxypropyl) (meth)acrylamide, N-(3-hydroxypropyl) (meth)acrylamide, N-(2-hydroxybutyl) (meth)acrylamide, N-(3-hydroxybutyl) (meth)acrylamide, N-(4-hydroxybutyl) (meth)acrylamide, and N-methyl-N-2-hydroxyethyl (meth)acrylamide.
[0149] The (meth)acrylamides include, for example, various N-alkoxyalkyl (meth)acrylamides, such as N-methoxymethyl (meth)acrylamide and N-butoxymethyl (meth)acrylamide.
[0150] In addition, examples of nitrogen atom-containing monomers other than the above-mentioned N-vinyl cyclic amides and the above-mentioned (meth)acrylamides include: amino group-containing monomers such as (meth)aminoethyl acrylate, dimethylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylate, and tert-butylaminoethyl (meth)acrylate; cyano group-containing monomers such as acrylonitrile and methacrylonitrile; (meth)acryloylmorpholine, N-vinylpiperazine, N-vinylpyrrole, N-vinylimidazole, N-vinylpyrazine, N-vinylmorpholine, N-vinylpyrazole, vinylpyridine, vinylpyrimidine, vinyl Azoles, vinyl isocyanates Heterocyclic monomers such as oxadiazole, vinylthiazole, vinylisothiazole, vinylpyridazine, (meth)acryloylpyrrolidone, (meth)acryloylpyrrolidine, (meth)acryloylpiperidine, N-methylvinylpyrrolidone, etc.; maleimide monomers such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, N-phenylmaleimide, etc.; N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, etc. Itaconimide monomers such as itaconimide, N-2-ethylhexyl itaconimide, N-lauryl itaconimide, and N-cyclohexyl itaconimide; succinimide monomers such as N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxyhexamethylenesuccinimide, and N-(meth)acryloyl-8-oxyoctamethylenesuccinimide; and isocyanate monomers such as 2-(meth)acryloyloxyethyl isocyanate.
[0151] [1-4. Other copolymerizable monomers]
[0152] Examples of copolymerizable monomers in acrylic polymers include, in addition to the above-mentioned nitrogen-containing monomers, hydroxyl-containing monomers, and alicyclic structure-containing monomers: alkoxyalkyl (meth)acrylates [e.g., 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, 4-ethoxybutyl (meth)acrylate, etc.]; epoxy-containing monomers [e.g., glycidyl (meth)acrylate , methyl glycidyl (meth)acrylate, etc.]; sulfonic acid group-containing monomers [such as sodium vinyl sulfonate, etc.]; phosphoric acid group-containing monomers; (meth)acrylates having an aromatic hydrocarbon group [such as phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, benzyl (meth)acrylate, etc.]; vinyl esters [such as vinyl acetate, vinyl propionate, etc.]; aromatic vinyl compounds [such as styrene, vinyl toluene, etc.]; olefins or dienes [such as ethylene, propylene, butadiene, isoprene, isobutylene, etc.]; vinyl ethers [such as vinyl alkyl ether, etc.]; vinyl chloride, etc.
[0153] [1-5. Hydrogenated polyolefin resins]
[0154] The acrylic adhesive composition of the present invention is preferably an acrylic adhesive composition with an acrylic polymer as the main component and with a hydrogenated polyolefin resin. The hydrogenated polyolefin resin is a material with a low dielectric constant. By being matched in the acrylic polymer of the present invention, the dielectric constant is reduced. In the touch panel of an optical component (touch sensor film) having metal wiring such as a metal mesh film and a silver nanowire film, the erroneous operation of the touch operation can be suppressed. In addition, it is possible to realize an adhesive layer with high flexibility when the low molecular weight of the acrylic polymer is not required. Even in the case of an optical component (touch sensor film) having metal wiring such as a metal mesh film and a silver nanowire film, it is possible to fully relax the stress with the metal wiring, thereby preventing uneven display, which is also preferred in this regard. In addition, the compatibility of the hydrogenated polyolefin resin and the acrylic polymer is also excellent, so the transparency of the adhesive layer of the present invention can be maintained at a higher level, which is preferred in this regard. The hydrogenated polyolefin resin can be used alone or in combination with more than two kinds.
[0155] The hydrogenated polyolefin resin is preferably a hydrogenated polyolefin resin that exhibits liquid fluidity at 25° C., from the perspective of being able to realize a highly flexible adhesive layer and being able to sufficiently relax the stress with the metal wiring even when an optical member (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is bonded to prevent display unevenness. The hydrogenated polyolefin resin exhibiting liquid fluidity at 25° C. means that the viscosity measured at 25° C. using a B-type viscometer is 10,000 mPa·s or less.
[0156] The hydrogenated polyolefin resin is obtained by reducing the carbon-carbon double bonds contained in the polyolefin resin by hydrogenation reaction. Since the hydrogenated polyolefin resin has fewer carbon-carbon double bonds in the molecule, it is less likely to be inhibited from polymerization when the acrylic adhesive composition of the present invention is cured by ultraviolet irradiation, and it is less likely to cause a decrease in polymerization rate and a decrease in molecular weight, so the adhesive reliability of the acrylic adhesive composition of the present invention at high temperature can be maintained at a high level.
[0157] From the viewpoint of less polymerization inhibition and adhesive reliability at high temperature, the hydrogenation rate of the hydrogenated polyolefin resin is preferably 90% or more, more preferably 95% or more, and further preferably 97% or more. There is no particular restriction on the upper limit of the hydrogenation rate, which is 100% in theory and can be 99.9% or less or 99.8% or less in practice. It should be noted that the hydrogenation rate of the hydrogenated polyolefin resin can be adjusted by using 1 The H-NMR measurement can be used to determine the amount of double bonds remaining in the hydrogenated polyolefin resin, for example.
[0158] From the viewpoint of less prone to polymerization inhibition and high temperature adhesion reliability, the iodine value (Ig / 100g) of the hydrogenated polyolefin resin is preferably 30 or less, more preferably 25 or less, and further preferably 20 or less. The lower limit of the iodine value is not particularly limited, and may be 0.1 or more, or 0.2 or more. It should be noted that the iodine value is a value measured in accordance with JIS K 0070-1992.
[0159] From the viewpoint of imparting appropriate stress relaxation and fluidity to the adhesive layer and improving compatibility with the acrylic polymer, the number average molecular weight (Mn) of the hydrogenated polyolefin resin is preferably 1000 to 5000. From the viewpoint of imparting appropriate stress relaxation and fluidity to the adhesive composition, the number average molecular weight (Mn) is preferably 1000 or more, more preferably 1500 or more, and further preferably 1800 or more. From the viewpoint of improving compatibility with the acrylic polymer and maintaining the transparency of the acrylic adhesive composition of the present invention at a higher level, the number average molecular weight (Mn) is preferably 5000 or less, more preferably 4800 or less, and further preferably 4600 or less.
[0160] From the perspective of imparting appropriate stress relaxation and fluidity to the adhesive layer, improving compatibility with acrylic polymers, maintaining high transparency, and being able to suppress haze, the polydispersity (Mw / Mn) of the hydrogenated polyolefin resin is preferably 2.0 or less, more preferably 1.8 or less. The lower limit of the polydispersity is not particularly limited, and in practical use, it can be 1.0 or 1.1 or more.
[0161] The number average molecular weight (Mn) and polydispersity (Mw / Mn) of the hydrogenated polyolefin resin are values determined by gel permeation chromatography (GPC) based on polystyrene standards.
[0162] The hydrogenated polyolefin resin preferably includes hydrogenated polyolefin. The acrylic pressure-sensitive adhesive composition of the present invention preferably includes hydrogenated polyolefin as the hydrogenated polyolefin resin, thereby reducing the dielectric constant and suppressing erroneous operation of touch operation in the touch panel.
[0163] The above-mentioned hydrogenated polyolefin is a hydrogenated product of a polymer (polyolefin) having a structural unit derived from an olefin. The hydrogenated polyolefin includes hydrogenated products of homopolymers and copolymers of α-olefins such as ethylene, propylene, 1-butene, isobutylene, and 1-hexene; diene compounds such as butadiene and isoprene; and aromatic vinyl compounds such as styrene. As the hydrogenated polyolefin, the hydrogenated product of the homopolymer or copolymer of the diene compound is preferred, for example, hydrogenated polybutadiene, hydrogenated polyisoprene, etc. The hydrogenated polyolefin can be used alone or in combination of two or more.
[0164] From the viewpoint of reducing the dielectric constant and suppressing erroneous operation of touch operation in the touch panel, the hydrogenated polyolefin-based resin preferably contains a hydrogenated polyolefin polyol in addition to the hydrogenated polyolefin.
[0165] The hydrogenated polyolefin polyol is a compound in which the terminal of the hydrogenated polyolefin is modified with a hydroxyl group. As the hydrogenated polyolefin polyol, a hydroxyl-modified product of a hydrogenated product of a homopolymer or copolymer of a diene compound is preferred, for example, hydrogenated polybutadiene polyol, hydrogenated polyisoprene polyol, etc. The hydrogenated polyolefin polyol can be used alone or in combination of two or more.
[0166] As the above-mentioned hydrogenated polyolefin and hydrogenated polyolefin polyol, hydrogenated polybutadiene polyol and hydrogenated polybutadiene polyol are respectively preferred from the perspectives of being able to realize a highly flexible adhesive layer and being able to sufficiently relax the stress with the metal wiring even when an optical component (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is bonded, thereby preventing display unevenness.
[0167] As the hydrogenated polybutadiene, preferably, it is a hydrogenated polybutadiene represented by the following formula (5), and as the hydrogenated polybutadiene polyol, preferably, it is a hydrogenated polybutadiene polyol represented by the following formula (6).
[0168]
[0169] In the above formula, m represents the degree of polymerization of the hydrogenated polybutadiene.
[0170] As hydrogenated polyolefins and hydrogenated polyolefin polyols, commercial products can be used. Commercial products of hydrogenated polyolefins include: trade names "BI-2000", "BI-3000" (all manufactured by Nippon Soda Co., Ltd.), etc. Commercial products of hydrogenated polyolefin polyols include: trade names "GI-1000", "GI-2000", "GI-3000" (all manufactured by Nippon Soda Co., Ltd.), trade name "EPOL" (manufactured by Idemitsu Kosan Co., Ltd.), etc.
[0171] The content of the hydrogenated polyolefin resin in the acrylic adhesive composition is not particularly limited. From the perspective of reducing the dielectric constant and suppressing erroneous operation of the touch operation in the touch panel, the content of the hydrogenated polyolefin resin is preferably 5 parts by weight or more, more preferably 10 parts by weight or more, further preferably 15 parts by weight or more, and may be 20 parts by weight or more relative to 100 parts by weight of the acrylic polymer. On the other hand, from the perspective of suppressing the increase in haze and ensuring higher transparency, and being able to highly maintain the adhesive force and adhesive reliability at high temperatures, the content of the hydrogenated polyolefin resin is preferably 40 parts by weight or less, more preferably 35 parts by weight or less, and further preferably 30 parts by weight or less.
[0172] The content of hydrogenated polyolefin in the acrylic adhesive composition is not particularly limited. From the viewpoint of reducing the dielectric constant and suppressing the erroneous operation of the touch operation in the touch panel, the content of hydrogenated polyolefin is preferably 0.5 parts by weight or more, more preferably 1 part by weight or more, and further preferably 1.5 parts by weight or more relative to 100 parts by weight of the acrylic polymer. On the other hand, from the viewpoint of suppressing the increase of haze and ensuring higher transparency, and being able to highly maintain the adhesive force and adhesive reliability at high temperatures, the content of hydrogenated polyolefin is preferably 20 parts by weight or less, more preferably 15 parts by weight or less, further preferably 12 parts by weight or less, and may also be 10 parts by weight or less or 5 parts by weight or less.
[0173] The content of the hydrogenated polyolefin polyol in the acrylic adhesive composition is not particularly limited. From the perspective of reducing the dielectric constant and suppressing erroneous operation of the touch operation in the touch panel, the content of the hydrogenated polyolefin polyol is preferably 1 part by weight or more, more preferably 3 parts by weight or more, and further preferably 5 parts by weight or more, and may also be 10 parts by weight or more or 20 parts by weight or more, relative to 100 parts by weight of the acrylic polymer. On the other hand, from the perspective of suppressing the increase in haze, ensuring higher transparency, and being able to highly maintain the adhesive force and adhesive reliability at high temperatures, the content of the hydrogenated polyolefin polyol is preferably 40 parts by weight or less, more preferably 35 parts by weight or less, further preferably 30 parts by weight or less, and particularly preferably 25 parts by weight or less.
[0174] The weight ratio of the content of hydrogenated polyolefin to the content of hydrogenated polyolefin polyol in the acrylic adhesive composition (hydrogenated polyolefin / hydrogenated polyolefin polyol) is not particularly limited. From the viewpoint of reducing the dielectric constant and suppressing the erroneous operation of the touch operation in the touch panel, it is preferably 1 / 99 or more, more preferably 2 / 98 or more, and may be 3 / 98 or more or 4 / 96 or more. In addition, from the viewpoint of suppressing the increase of haze and ensuring higher transparency, the above ratio is preferably 90 / 10 or less, more preferably 80 / 20 or less, further preferably 70 / 30 or less, and may be 55 / 45 or less, 45 / 55 or less, or 30 / 70 or less.
[0175] [1-6. Multifunctional (meth)acrylate]
[0176] The acrylic pressure-sensitive adhesive composition of the present invention preferably further contains a polyfunctional (meth)acrylate. The polyfunctional (meth)acrylate functions as a crosslinking component, and the pressure-sensitive adhesive composition tends to have appropriate cohesive strength.
[0177] Examples of the multifunctional (meth)acrylate include hexanediol di(meth)acrylate, butanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl (meth)acrylate, vinyl (meth)acrylate, divinylbenzene, epoxy acrylate, polyester acrylate, and urethane acrylate. It should be noted that the multifunctional (meth)acrylate may be used alone or in combination of two or more.
[0178] The content (ratio) of the multifunctional (meth) acrylate is not particularly limited. From the viewpoint that the adhesive layer has a moderate cohesive force, it is preferably 0.001 parts by weight or more, more preferably 0.002 parts by weight or more, further preferably 0.005 parts by weight or more, and may be 0.01 parts by weight or more, relative to 100 parts by weight of the acrylic polymer. In addition, from the perspective of being able to achieve a highly flexible adhesive layer and being able to fully relax the stress with the metal wiring to prevent uneven display, the content (ratio) of the multifunctional (meth) acrylate is preferably 0.5 parts by weight or less, more preferably 0.35 parts by weight or less, further preferably 0.2 parts by weight or less, and may be 0.1 parts by weight or less, relative to 100 parts by weight of the acrylic polymer.
[0179] [1-7. Silane coupling agent]
[0180] The acrylic adhesive composition of the present invention preferably further contains a silane coupling agent. When the adhesive composition contains a silane coupling agent, it is preferred because excellent adhesion to glass (especially excellent adhesion reliability to glass under high temperature and high humidity) can be easily obtained.
[0181] As the above-mentioned silane coupling agent, there is no particular limitation, and examples thereof include: γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-phenylaminopropyltrimethoxysilane, etc. Among them, γ-glycidoxypropyltrimethoxysilane is preferred. In addition, as the above-mentioned silane coupling agent, for example, commercial products such as the trade name "KBM-403" (manufactured by Shin-Etsu Chemical Co., Ltd.) can also be mentioned. It should be noted that the silane coupling agent can be used alone or in combination of two or more.
[0182] The content of the silane coupling agent is not particularly limited, but is preferably 0.01 to 1 part by weight, more preferably 0.03 to 0.5 parts by weight, based on 100 parts by weight of the acrylic polymer, from the viewpoint of improving the reliability of adhesion to glass.
[0183] [1-8. Cross-linking agent]
[0184] As described above, the acrylic pressure-sensitive adhesive composition of the present invention is preferably not a solvent-based composition, that is, preferably contains no or substantially no crosslinking agent.
[0185] Examples of the crosslinking agent include isocyanate crosslinking agents, epoxy crosslinking agents, melamine crosslinking agents, peroxide crosslinking agents, urea crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, carbodiimide crosslinking agents, Azoline crosslinking agents, aziridine crosslinking agents, amine crosslinking agents, etc. In particular, the acrylic adhesive composition of the present invention preferably contains no or substantially no isocyanate crosslinking agents and / or epoxy crosslinking agents as crosslinking agents, and preferably contains no or substantially no isocyanate crosslinking agents.
[0186] Examples of the isocyanate crosslinking agent (polyfunctional isocyanate compound) include lower aliphatic polyisocyanates such as 1,2-ethylene diisocyanate, 1,4-butylene diisocyanate, and 1,6-hexamethylene diisocyanate; alicyclic polyisocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, isophorone diisocyanate, hydrogenated toluene diisocyanate, and hydrogenated xylene diisocyanate; and aromatic polyisocyanates such as 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4′-diphenylmethane diisocyanate, and xylylene diisocyanate. In addition, examples of the isocyanate crosslinking agent include commercially available products such as trimethylolpropane / toluene diisocyanate adduct [manufactured by Nippon Polyurethane Industries, Ltd., trade name “CORONATE L”], trimethylolpropane / hexamethylene diisocyanate adduct [manufactured by Nippon Polyurethane Industries, Ltd., trade name “CORONATE HL”], and trimethylolpropane / xylylene diisocyanate adduct [manufactured by Mitsui Chemicals, Inc., trade name “TAKENATE D-110N”].
[0187] Examples of the epoxy crosslinking agent (polyfunctional epoxy compound) include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidyl aniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, Sorbitol polyglycidyl ether, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, diglycidyl adipate, diglycidyl phthalate, tris(2-hydroxyethyl)isocyanuric acid triglycidyl ester, resorcinol diglycidyl ether, bisphenol S diglycidyl ether, and epoxy resins having two or more epoxy groups in the molecule. In addition, as the above-mentioned epoxy crosslinking agent, for example, commercial products such as the trade name "TETRAD C" manufactured by Mitsubishi Gas Chemical Co., Ltd. can also be mentioned.
[0188] In the acrylic adhesive composition of the present invention, "substantially free of crosslinking agent" means that the crosslinking agent is not actively mixed except for the case where the crosslinking agent is inevitably mixed. Specifically, relative to the total amount of the adhesive composition (total weight, 100 weight %), the content of the crosslinking agent in the adhesive composition is 1.0 weight % or less (preferably 0.5 weight % or less, more preferably 0.2 weight % or less), and it can be said that it is substantially free of crosslinking agent. In addition, relative to the total amount of monomer components constituting the acrylic polymer (100 weight parts), the content of the crosslinking agent is preferably 0.05 weight part or less (for example, 0 to 0.05 weight part), more preferably 0.01 weight part or less (for example, 0 to 0.01 weight part), and more preferably 0.001 weight part or less (for example, 0 to 0.001 weight part), and it can also be said that it is substantially free of crosslinking agent.
[0189] [1-9. Additives]
[0190] The acrylic adhesive composition of the present invention may contain known additives such as a crosslinking accelerator, a tackifying resin (rosin derivatives, polyterpene resins, oil-soluble phenol resins, etc.), an anti-aging agent, a filler, a colorant (pigment, dye, etc.), an ultraviolet absorber, a chain transfer agent, a plasticizer, a softener, a surfactant, an antistatic agent, a rust inhibitor, and an antioxidant as needed within a range that does not impair the characteristics of the present invention. From the viewpoint of suppressing the increase in the haze of the adhesive layer of the present invention, the acrylic adhesive composition of the present invention preferably does not substantially contain a rust inhibitor or an antioxidant. It should be noted that such additives may be used alone or in combination of two or more.
[0191] From the viewpoint of suppressing the increase in the haze of the adhesive layer of the present invention, the acrylic adhesive composition of the present invention preferably does not substantially contain an antioxidant. "Substantially containing no antioxidant" means that the antioxidant is not actively mixed except for the case where the antioxidant is inevitably mixed. Specifically, relative to the total amount of the adhesive composition (total weight, 100 weight%), the content of the antioxidant in the adhesive composition is 1.0 weight% or less (preferably 0.5 weight% or less, more preferably 0.2 weight% or less), and it can be said that it does not substantially contain. In addition, relative to the total amount of monomer components constituting the acrylic polymer (100 weight parts), the content of the antioxidant is preferably, for example, 0.5 weight parts or less (for example, 0 to 0.5 weight parts), 0.05 weight parts or less (for example, 0 to 0.05 weight parts), more preferably 0.01 weight parts or less (for example, 0 to 0.01 weight parts), and more preferably 0.001 weight parts or less (for example, 0 to 0.001 weight parts) It can also be said that it does not substantially contain.
[0192] [1-10. Preparation of acrylic adhesive composition]
[0193] The acrylic adhesive composition of the present invention can be prepared by mixing an acrylic polymer, a hydrogenated polyolefin resin as required, a multifunctional (meth) acrylate, a silane coupling agent, and other additives and stirring them uniformly. At this time, from the viewpoint of adjusting the elastic modulus of the adhesive layer, the monomer components constituting the acrylic polymer can be matched. In the case of using the monomer components constituting the acrylic polymer in order to adjust the elastic modulus, in order to maintain the above-mentioned characteristics of the adhesive layer, it is preferred to prepare the acrylic polymer using a monomer mixture other than the monomer components used. There is no particular restriction on the monomer components used to adjust the elastic modulus, for example, the above-mentioned functional group-containing monomers are preferred, and the above-mentioned hydroxyl-containing monomers are more preferred.
[0194] The amount of the monomer component used to adjust the elastic modulus is not particularly limited, but is preferably 5 to 30 parts by weight, more preferably 10 to 20 parts by weight, relative to 100 parts by weight of all monomer units of the acrylic polymer (the total amount of monomer components constituting the acrylic polymer).
[0195] [2. Adhesive sheet]
[0196] The pressure-sensitive adhesive sheet of the present invention is not particularly limited in other respects as long as it has the pressure-sensitive adhesive layer of the present invention (pressure-sensitive adhesive layer formed from the acrylic pressure-sensitive adhesive composition of the present invention).
[0197] The adhesive sheet of the present invention can be a double-sided adhesive sheet with both sides being the adhesive layer surface, or a single-sided adhesive sheet with only one side being the adhesive layer surface. Wherein, from the viewpoint of laminating 2 members to each other, it is preferably a double-sided adhesive sheet. It should be noted that in this specification, when referred to as "adhesive sheet", a band-shaped adhesive sheet, i.e. "adhesive tape" is also included. In addition, in this specification, the adhesive layer surface is sometimes referred to as "adhesive face".
[0198] The pressure-sensitive adhesive sheet of the present invention may be provided with a release liner on the pressure-sensitive adhesive surface until use.
[0199] The adhesive sheet of the present invention may be a so-called "substrate-free" adhesive sheet (hereinafter sometimes referred to as "substrate-free adhesive sheet") that does not have a substrate (substrate layer), or may be a type of adhesive sheet having a substrate (hereinafter sometimes referred to as "adhesive sheet with substrate"). As the above-mentioned substrate-free adhesive sheet, for example, there can be mentioned: a double-sided adhesive sheet comprising only the above-mentioned adhesive layer, a double-sided adhesive sheet comprising the above-mentioned adhesive layer and an adhesive layer other than the above-mentioned adhesive layer (sometimes referred to as "other adhesive layers"), etc. On the other hand, as an adhesive sheet with a substrate, there can be mentioned: an adhesive sheet having the above-mentioned adhesive layer on at least one side of the substrate, etc. Among them, a substrate-free adhesive sheet (substrate-free double-sided adhesive sheet) is preferred, and a substrate-free double-sided adhesive sheet comprising only the above-mentioned adhesive layer is more preferred. It should be noted that the above-mentioned "substrate (substrate layer)" does not include a release liner that is peeled off when the adhesive sheet is used (pasted).
[0200] Figure 1 1 is a schematic diagram (cross-sectional view) showing a specific example of a preferred embodiment of the adhesive sheet of the present invention, wherein 1 represents the adhesive sheet, 10 represents the adhesive layer of the present invention, and 11 and 12 represent release liners. Figure 1 In the figure, the pressure-sensitive adhesive sheet 1 is a double-sided pressure-sensitive adhesive sheet without a substrate, and both pressure-sensitive adhesive surfaces of the pressure-sensitive adhesive layer 10 are protected by release liners 11 and 12 .
[0201] Since the adhesive layer 10 is composed of the adhesive layer of the present invention, even if the adhesive sheet 1 is left under high temperature and high humidity conditions and then returns to room temperature, white turbidity due to humidity is unlikely to occur.
[0202] The thickness (total thickness) of the adhesive sheet of the present invention is not particularly limited, preferably 12 μm to 350 μm, more preferably 12 μm to 300 μm. When the thickness is above a certain value, in a touch panel having an optical component (touch sensor film) having metal wiring such as a metal mesh film and a silver nanowire film, it is possible to fully relax the stress with the metal wiring, thereby preventing uneven display, which is preferred. In addition, when the thickness is below a certain value, it is easy to maintain an excellent appearance during manufacture and roll storage, and it is not easy to produce glue contamination during cutting processing, which is preferred at this point. It should be noted that the thickness of the adhesive sheet of the present invention does not include the thickness of the release liner.
[0203] The adhesive sheet of the present invention is preferably manufactured according to known or customary manufacturing methods, but is not particularly limited. For example, in the case where the adhesive sheet of the present invention is a substrate-free adhesive sheet, the above-mentioned adhesive layer is obtained by utilizing the above-mentioned method to form the above-mentioned adhesive layer on a release liner. In addition, in the case where the adhesive sheet of the present invention is an adhesive sheet with a substrate, the above-mentioned adhesive layer can be obtained by directly forming the above-mentioned adhesive layer on the surface of the substrate (direct method), and the above-mentioned adhesive layer can also be obtained by first forming the above-mentioned adhesive layer on the release liner, and then transferring (laminating) it to the substrate, thereby arranging the above-mentioned adhesive layer on the substrate and obtaining (transfer method).
[0204] The adhesive sheet of the present invention may have other layers in addition to the above-mentioned adhesive layer. As other layers, for example, other adhesive layers (adhesive layers other than the adhesive layer of the present invention), intermediate layers, primer layers, etc. may be mentioned. It should be noted that the adhesive sheet of the present invention may have more than two other layers.
[0205] As the substrate in the case where the adhesive sheet of the present invention is an adhesive sheet with a substrate, there is no particular limitation, and examples thereof include: various optical films such as plastic films, anti-reflection (AR) films, polarizing plates, and phase difference plates. As materials for the above-mentioned plastic films, for example, polyester resins such as polyethylene terephthalate (PET), acrylic resins such as polymethyl methacrylate (PMMA), polycarbonates, triacetyl cellulose (TAC), polysulfones, polyarylates, polyimides, polyvinyl chloride, polyvinyl acetate, polyethylene, polypropylene, ethylene-propylene copolymers, plastic materials such as cyclic olefin polymers such as "ARTON (cyclic olefin polymer, manufactured by JSR Co., Ltd.)", and "ZEONOR (cyclic olefin polymer, manufactured by Japan Zeon Co., Ltd.)". It should be noted that these plastic materials can be used alone or in combination with more than two kinds. In addition, the above-mentioned "substrate" refers to the part that is attached to the adherend together with the adhesive layer when the adhesive sheet is attached to the adherend. The release liner that is peeled off when the pressure-sensitive adhesive sheet is used (when attached) is not included in the “substrate”.
[0206] The substrate is preferably transparent. The total light transmittance of the substrate in the visible light wavelength range (according to JIS K7361-1) is not particularly limited, preferably 85% or more, more preferably 88% or more. In addition, the haze of the substrate (according to JIS K7136) is not particularly limited, preferably 1.0% or less, more preferably 0.8% or less. As such a transparent substrate, for example, PET film, trade name "ARTON", trade name "ZEONOR" and other non-oriented films can be cited.
[0207] The thickness of the substrate is not particularly limited, and is preferably 12 μm to 500 μm, for example. It should be noted that the substrate may have any form of a single layer or a multilayer. In addition, the surface of the substrate may be appropriately subjected to a known and commonly used surface treatment such as a physical treatment such as a corona discharge treatment or a plasma treatment, or a chemical treatment such as a primer treatment.
[0208] Adhesive sheet of the present invention can be provided with release liner on adhesive face until before use.It should be noted that, when adhesive sheet of the present invention is a double-sided adhesive sheet, each adhesive face can be protected by 2 release liners respectively, and can also be protected by 1 release liner of the release face with the form of winding into a roll by two sides.Release liner is used as the protective material of adhesive layer, and is peeled off when being pasted on adherend.In addition, when adhesive sheet of the present invention is a substrate-free adhesive sheet, release liner also plays the effect of the support as adhesive layer.It should be noted that, it is also possible not to set release liner.
[0209] As the above-mentioned release liner, there is no particular restriction, for example, a release liner having a release layer (release treatment layer) on at least one surface of the release liner substrate, a release liner with low adhesiveness containing a fluorine-containing polymer, a release liner with low adhesiveness containing a non-polar polymer, etc. As the above-mentioned fluorine-containing polymer, there is no particular restriction, for example, polytetrafluoroethylene, polychlorotrifluoroethylene, polyvinyl fluoride, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, chlorofluoroethylene-vinylidene fluoride copolymer, etc. In addition, as the above-mentioned non-polar polymer, there is no particular restriction, for example, olefin resins such as polyethylene (PE) and polypropylene (PP), etc. can be mentioned. Among them, it is preferred to use a release liner having a release layer on at least one surface of the release liner substrate.
[0210] The release liner substrate is not particularly limited, and examples thereof include plastic films. Examples of such plastic films include polyester resins such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), and polybutylene terephthalate (PBT); olefin resins containing α-olefin as a monomer component such as polyethylene (PE), polypropylene (PP), polymethylpentene (PMP), ethylene-propylene copolymer, and ethylene-vinyl acetate copolymer (EVA); polyvinyl chloride (PVC); vinyl acetate resins; polycarbonate (PC); polyphenylene sulfide (PPS); amide resins such as polyamide (nylon) and wholly aromatic polyamide (aramid); polyimide resins; and polyetheretherketone (PEEK). Among them, from the viewpoints of processability, availability, workability, dustproofness, cost, and the like, a plastic film formed of a polyester resin is preferred, and a PET film is more preferred.
[0211] There are no particular restrictions on the release agent constituting the release layer, and examples thereof include silicone release agents, fluorine-containing release agents, long-chain alkyl release agents, molybdenum sulfide and other release agents. Among them, silicone release agents are preferred from the viewpoint of release control and stability over time. It should be noted that the release agent may be used alone or in combination of two or more.
[0212] The release layer may be a single layer, or may have a laminated structure in which two or more layers are laminated, within a range not impairing the characteristics of the present invention.
[0213] Among them, as an example of a preferred specific structure of the release liner, the following structure can be cited: a PET film is used as a release liner substrate, and a release layer based on a silicone-based release treatment agent is provided on at least one surface of the release liner substrate. It should be noted that, of the two surfaces of the release liner, the surface on the opposite side to the side in contact with the adhesive layer, on which the release layer is not provided, is sometimes referred to as the "back side" of the release liner.
[0214] From the viewpoint of ensuring punching processability and operability, and increasing thickness while maintaining flexibility, the release liner may be laminated with a carrier material on the back. Such a carrier material is not particularly limited, and examples thereof include: a structure obtained by laminating two layers of a PET film substrate with an adhesive layer therebetween, a structure obtained by laminating two layers of a COP film substrate and a PET film substrate with an adhesive layer therebetween, etc. It should be noted that the release liner may not have a carrier material.
[0215] In addition, from the viewpoint of suppressing static electricity generated when the release liner is transported and when it is peeled off, and reducing the adhesion and mixing of foreign matter, the release liner may have a conductive treatment layer on the release layer and / or the back surface. Such a conductive treatment layer is not particularly limited, and examples thereof include a coating treatment layer having a composite of poly(3,4-ethylenedioxythiophene) (PEDOT) and polystyrene sulfonic acid (PSS) as a conductive polymer as a main component. It should be noted that the release liner may not have a conductive treatment layer.
[0216] The release liner can be manufactured by a known conventional method. The carrier material and the conductive treatment layer can be prepared by laminating on the release layer and / or the back surface of the release liner using a known method. In addition, the release liner of the present invention can have other layers (e.g., an intermediate layer, a primer layer, etc.) within a range that does not impair the effects of the present invention.
[0217] The thickness of the release liner is not particularly limited, but is preferably 12 μm to 200 μm, more preferably 25 μm to 150 μm, and even more preferably 38 μm to 125 μm, from the viewpoint of cost and handleability of the pressure-sensitive adhesive sheet during lamination.
[0218] In addition, when the adhesive sheet of the present invention is a double-sided adhesive sheet of a double release liner type, a release liner is provided on one adhesive surface and a release liner is also provided on the other adhesive surface. In this case, the two release liners are preferably release liners each having only one surface as a release layer (particularly a release liner having a release layer containing a silicone release agent on one surface of a plastic substrate). In addition, the release liner is provided in a manner that the release layer contacts the adhesive surface.
[0219] In addition, when the adhesive sheet of the present invention is a double-release liner type double-sided adhesive sheet, the peeling force of the preferred 2 release liners is provided with a difference. For example, when the adhesive sheet of the present invention is a double-release liner type double-sided adhesive sheet, preferably a release liner is used for the adhesive surface (also referred to as "the first side") used first (pasting), and another release liner is used for the adhesive surface (also referred to as "the second side") used later (pasting). Therefore, preferably a release liner is used as a release liner of the "light peeling side" that can be peeled off with less force (peeling force), and another release liner is used as a release liner of the "heavy peeling side" that needs a larger force (peeling force) when peeling from the adhesive layer. It should be noted that in this specification, the release liner of the above-mentioned light peeling side is sometimes referred to as a "light peeling liner", and the release liner of the above-mentioned heavy peeling side side is sometimes referred to as a "heavy peeling liner".
[0220] It should be noted that, when adhesive sheet of the present invention is a single release liner type double-sided adhesive sheet, a release liner is set on an adhesive face, by winding up another adhesive face of an adhesive body is also protected by this release liner. When adhesive sheet of the present invention is a single release liner type, the surface of the preferred release liner is a release layer (peeling treatment layer). In addition, sometimes the release layer of a side contacted with the adhesive face by winding up in two release layers of the above-mentioned release liner is particularly referred to as "back side release layer". Usually, the back side release layer side of the release liner is used for " the first side " of the double-sided adhesive sheet.
[0221] The adhesive layer of the present invention is endowed with stress relaxation properties, and therefore, it is preferred from the viewpoint of suppressing the roughening, deformation, and stickiness of the adhesive surface of the adhesive layer when the release liner is peeled off, and enabling the stable use of the adhesive sheet. It should be noted that stickiness is a vibration phenomenon generated on the release surface, which causes damage to the adherend and breaks it, or locally produces adhesive residue on the adherend.
[0222] In the case where the pressure-sensitive adhesive sheet of the present invention is a double-sided pressure-sensitive adhesive sheet, from the perspective of suppressing the roughening, deformation, and stickiness of the adhesive surface of the pressure-sensitive adhesive layer when the release liner is peeled off and enabling the pressure-sensitive adhesive sheet to be used stably, the release force (release liner release force) of the first side (light release side) of the release liner on the pressure-sensitive adhesive layer is preferably 0.01N / 50mm to 0.5N / 50mm, preferably 0.05N / 50mm to 0.25N / 50mm, and the release force (release liner release force) of the second side (heavy release side) of the release liner on the pressure-sensitive adhesive layer (e.g., the acrylic pressure-sensitive adhesive layer, the rubber pressure-sensitive adhesive layer, etc.) is preferably 0.1N / 50mm to 1.00N / 50mm, preferably 0.2N / 50mm to 0.85N / 50mm, the release force of the release liner on the heavy release side is always greater than the release force of the release liner on the light release side, and there is a release difference of about 1.1 times to about 10.0 times.
[0223] In particular, when the adhesive sheet of the present invention is a double-sided adhesive sheet, from the perspective of suppressing the so-called accidental separation phenomenon, the roughening, deformation, and stickiness of the adhesive surface of the adhesive layer when the release liner is peeled off, and enabling the stable use of the adhesive sheet, the difference between the peeling force of the heavy release liner on the adhesive layer (release liner peeling force) and the peeling force of the light release liner on the adhesive layer (release liner peeling force) is preferably 0.01 N / 50 mm or more, more preferably 0.02 N / 50 mm or more, further preferably 0.05 N / 50 mm or more, and particularly preferably 0.06 N / 50 mm or more.
[0224] It should be noted that the release liner peel strength is the 180° peel adhesive strength of the release liner to the pressure-sensitive adhesive layer measured by a 180° peel test. It should be noted that the pulling speed was 300 mm / min.
[0225] The adhesive sheet of the present invention has the adhesive layer of the present invention (adhesive layer formed by the acrylic adhesive composition of the present invention), so even if it is placed under high temperature and high humidity conditions and then restored to room temperature, it is not easy to produce humidified white turbidity. In addition, it is excellent in flexibility, and even when an optical component (touch sensor film) with metal wiring such as a metal mesh film and a silver nanowire film is attached, it can prevent uneven display of a display device or an input device. In addition, it has excellent adhesiveness, foaming peeling resistance, and height difference tracking.
[0226] Therefore, the adhesive sheet of the present invention can be used in an image display device, in a touch panel in which a touch sensor is assembled in these image display devices, to paste optical components such as a polarizing film, a phase difference film, an optical compensation film, a touch sensor film, and a cover film on the image display panel, or can be used to paste these optical components to each other. In addition, the adhesive sheet of the present invention can also be used for adherends that are prone to foaming at the interface at high temperatures. For example, polymethyl methacrylate resin (PMMA) sometimes contains unreacted monomers and is prone to foaming caused by foreign matter at high temperatures. In addition, polycarbonate (PC) is prone to outgassing of water and carbon dioxide at high temperatures. The adhesive sheet of the present invention has excellent resistance to foaming and peeling, so it can be used for plastic adherends containing such resins.
[0227] In addition, the adhesive sheet of the present invention can be used for adherends with a large linear expansion coefficient in addition to adherends with a small linear expansion coefficient. It should be noted that the adherends with a small linear expansion coefficient are not particularly limited, and examples thereof include glass plates (linear expansion coefficient: 0.3×10 -5 / ℃~0.8×10 -5 / ℃), polyethylene terephthalate substrate (PET film, linear expansion coefficient: 1.5×10 -5 / ℃~2×10 -5 / °C). In addition, there are no particular restrictions on the adherend having a large linear expansion coefficient, and examples thereof include: a resin substrate having a large linear expansion coefficient, and more specifically, a polycarbonate resin substrate (PC, linear expansion coefficient: 7×10 -5 / ℃~8×10 -5 / ℃)、PMMA、Linear expansion coefficient:7×10 -5 / ℃~8×10 -5 / ℃), cycloolefin polymer substrate (COP, linear expansion coefficient: 6×10 -5 / ℃~7×10 -5 / °C), trade name “ZEONOR” (manufactured by Zeon Co., Ltd.), trade name “ARTON” (manufactured by JSR Corporation), etc.
[0228] The adhesive sheet of the present invention can be used for bonding an adherend with a small linear expansion coefficient to an adherend with a large linear expansion coefficient. Specifically, the adhesive sheet of the present invention is preferably used for bonding a glass adherend (e.g., a glass plate, chemically strengthened glass, a glass lens, etc.) to the above-mentioned resin substrate with a large linear expansion coefficient.
[0229] It can be seen that the adhesive sheet of the present invention can be used for bonding adherends of various materials to each other, and can be used in particular for bonding a glass adherend to a plastic adherend.
[0230] In addition, the adhesive sheet of the present invention can be used for adherends with smooth surfaces, and can also be used for adherends with height differences on the surface, such as optical components (touch sensor films) having metal wiring such as metal mesh films and silver nanowire films. In particular, even if at least one of a glass adherend and the above-mentioned resin substrate with a large linear expansion coefficient has a height difference on the surface, the adhesive sheet of the present invention can be used for bonding the glass adherend to the above-mentioned resin substrate with a large linear expansion coefficient.
[0231] The adhesive sheet of the present invention is preferably used for the manufacture of portable electronic devices. Examples of the portable electronic devices include: mobile phones, PHS, smart phones, tablet computers (tablet computers), mobile computers (mobile PCs), portable information terminals (PDAs), electronic notepads, portable broadcast receivers such as portable TVs or portable radios, portable game consoles, portable audio players, portable DVD players, cameras such as digital cameras, and portable video cameras.
[0232] The adhesive sheet of the present invention is preferably used, for example, for pasting components or modules constituting portable electronic devices to each other, fixing components or modules constituting portable electronic devices to a housing, etc. More specifically, it can be cited as follows: lamination of protective glass or lens (especially glass lens) with touch panel or touch sensor film (especially touch sensor film with metal wiring such as metal mesh film and silver nanowire film), lamination of polarizing film with touch panel or touch sensor, lamination of display panel with touch panel or touch sensor film, fixing of protective glass or lens (especially glass lens) to housing, fixing of display panel to housing, fixing of input device such as sheet keyboard or touch panel to housing, lamination of protective panel of information display part to housing, lamination of housings to each other, lamination of housing to decorative sheet, fixing or lamination of various components or modules constituting portable electronic devices, etc. It should be noted that in this specification, display panel refers to a structure consisting of at least lens (especially glass lens) and touch panel. In addition, the lens in this specification is a concept including both transparent bodies showing the refraction of light and transparent bodies without the refraction of light. That is, the lens in this specification also includes a simple window panel without a refractive effect.
[0233] In addition, the adhesive sheet of the present invention is preferably used for optical purposes. That is, the adhesive sheet of the present invention is preferably an optical adhesive sheet for optical purposes. More specifically, for example, it is preferably used for the purpose of laminating optical components (optical component lamination), the manufacture of products (optical products) using the above optical components, etc.
[0234] [3. Optical member with adhesive layer, image display device, touch panel]
[0235] The optical component with adhesive layer of the present invention is not particularly limited in other aspects as long as it is an optical component with adhesive layer having the adhesive sheet of the present invention attached to at least one side of the optical component. It should be noted that the adhesive layer of the optical component with adhesive layer of the present invention may be provided with a release liner on the adhesive surface until use, or may not be provided with a release liner.
[0236] The optical member with an adhesive layer of the present invention is formed by attaching the adhesive sheet of the present invention, so even if it is placed under high temperature and high humidity conditions and then returned to room temperature, it is not easy to produce humidified white turbidity. In addition, it has high flexibility and can fully relax the stress with the metal wiring to prevent display unevenness. In addition, the adhesion reliability, especially the adhesion reliability at high temperature, is excellent.
[0237] The optical component with an adhesive layer of the present invention may be an optical component with an adhesive layer in which the adhesive sheet of the present invention is attached to an optical component (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film. In this case, the adhesive sheet of the present invention is preferably attached to the surface of the touch sensor film on the side having the above-mentioned metal wiring.
[0238] Figure 2 It is a schematic diagram (cross-sectional view) showing a specific example of a preferred embodiment of the pressure-sensitive adhesive layer-attached optical member of the present invention.
[0239] exist Figure 2 In (a), 2A represents an optical component with an adhesive layer, 20 represents the adhesive layer of the present invention, 21 represents an optical component, and 22 represents a release liner. The adhesive layer 20 is laminated on one side of the optical component 21, and the adhesive surface of the adhesive layer 20 on the opposite side of the optical component 21 is protected by the release liner 22.
[0240] exist Figure 2 In (b), 2B represents an optical component with an adhesive layer (touch sensor film with an adhesive layer), 20 represents the adhesive layer of the present invention, 23 represents the touch sensor film, 22 represents a release liner, and 24 represents a metal wiring. The adhesive layer 20 is laminated on the surface of the touch sensor film 23 on which the metal wiring 24 is formed, and the adhesive surface of the adhesive layer 20 on the opposite side to the touch sensor film 23 is protected by the release liner 22.
[0241] Since the pressure-sensitive adhesive layer 20 is composed of the pressure-sensitive adhesive layer of the present invention, the pressure-sensitive adhesive layer-attached optical member 2A and the pressure-sensitive adhesive layer-attached touch sensor film 2B are less likely to become humidified and white turbid even when they are returned to room temperature after being placed under high-temperature and high-humidity conditions.
[0242] From the viewpoint of obtaining a better anticorrosion effect, the pressure-sensitive adhesive layer-attached optical member preferably further has a pressure-sensitive adhesive layer attached to the surface of the optical member opposite to the side having the pressure-sensitive adhesive layer. The pressure-sensitive adhesive layer is preferably the pressure-sensitive adhesive layer of the present invention.
[0243] There are no particular restrictions on the material constituting the metal wiring, and examples thereof include metals such as titanium, silicon, niobium, indium, zinc, tin, gold, silver, copper, aluminum, cobalt, chromium, nickel, lead, iron, palladium, platinum, tungsten, zirconium, tantalum, and hafnium. In addition, materials containing two or more of these metals and alloys with these metals as main components may also be mentioned. Among them, from the aspect of electrical conductivity, gold, silver, and copper are preferred, and from the aspect of electrical conductivity and cost, silver and copper are more preferred. That is, the metal wiring is preferably silver wiring and / or copper wiring, in particular copper mesh wiring, silver mesh wiring, and silver nanowires. In addition, for higher rust prevention, an oxide film or a metal coating film may be provided on the metal wiring.
[0244] Optical components refer to components with optical properties (e.g., polarization, light refraction, light scattering, light reflection, light transmittance, light absorption, light diffraction, optical rotation, visual recognition, etc.). As substrates constituting the above-mentioned optical components, there are no particular restrictions, for example, substrates constituting devices (optical devices) such as image display devices and touch panels or substrates used in these devices, for example, polarizing films, wavelength plates, phase difference films, optical compensation films, brightness enhancement films, light guide plates, reflective films, anti-reflective films, hard coating films (films hard-coated on at least one side of plastic films such as PET films), transparent conductive films (e.g., plastic films having an ITO layer on the surface (preferably PET-ITO, polycarbonate, cycloolefin polymers, etc. ITO films)), design films, decorative films, surface protection plates, prisms, lenses, color filters, transparent substrates (glass sensors, glass display panels (LCDs, etc.), glass substrates such as glass plates with transparent electrodes, etc.), and substrates stacked therefrom (sometimes collectively referred to as "functional films"), etc. In addition, these films may have metal wiring such as a metal nanowire layer and a conductive polymer layer. In addition, metal fine wires may be screen-printed on these films. It should be noted that the above-mentioned "plate" and "film" each include plate-like, film-like, sheet-like and other forms. For example, "polarizing film" includes "polarizing plate and "polarizer". In addition, "film" includes film sensors, etc.
[0245] In particular, the adhesive sheet of the present invention can be suitable for an optical component (touch sensor film) having a transparent conductive film (metal mesh film, silver nanowire film) in which the above-mentioned metal wiring is a metal mesh wiring or a silver nanowire, especially a metal mesh film. When an optical component having metal wiring such as a metal mesh film or a silver nanowire film is bonded by an adhesive sheet, there is a problem that uneven display is easily generated at the periphery of the image display panel due to stress and strain of the adhesive applied to the periphery of the metal wiring. Therefore, in order to prevent uneven display, the adhesive layer of the adhesive sheet bonded to the optical component having metal wiring requires flexibility to relax the stress of the metal wiring.
[0246] In the adhesive sheet of the present invention, the adhesive layer of the present invention has high flexibility, and even when a film having metal wiring such as a metal mesh film or a silver nanowire film is attached, the stress between the metal wiring and the adhesive layer can be fully relaxed, thereby preventing uneven display. In addition, even if the image display device or touch panel having the adhesive sheet of the present invention is placed under high temperature and high humidity conditions and then returned to room temperature, it is not easy to produce humidified white turbidity, and the visual recognition of the image display device can be maintained.
[0247] Examples of the image display device include a liquid crystal display device, an organic EL (electroluminescence) display device, a PDP (plasma display panel), and electronic paper.
[0248] There are no particular restrictions on the substrate constituting the optical component, and examples thereof include substrates (e.g., sheet-shaped, film-shaped, plate-shaped substrates, etc.) comprising glass, acrylic resin, polycarbonate, polyethylene terephthalate, cycloolefin polymer, metal thin film, etc. It should be noted that, as described above, the "optical component" in the present invention also includes components (design films, decorative films, surface protection films, etc.) that play a decorative and protective role while maintaining the visual recognizability of the image display device and the touch panel.
[0249] If the pressure-sensitive adhesive sheet of the present invention is a pressure-sensitive adhesive sheet with a substrate and the pressure-sensitive adhesive sheet constitutes a member having optical properties, the substrate can be regarded as the same as the substrate, and the pressure-sensitive adhesive sheet can also be regarded as the pressure-sensitive adhesive layer optical member of the present invention.
[0250] When the PSA sheet of the present invention is a PSA sheet with a substrate and the functional film is used as the substrate, the PSA sheet of the present invention can be used as an "adhesive functional film" having the PSA layer on at least one side of the functional film.
[0251] Figure 3 It is a schematic diagram (cross-sectional view) showing a specific example of a preferred embodiment of the image display device of the present invention.
[0252] exist Figure 3In the figure, 3 represents an image display device, 30 and 31 represent adhesive layers of the present invention, 32 represents an image display panel, 33 represents a polarizing film, and 34 represents a transparent substrate. The image display device 3 is stacked with an image display panel 32, an adhesive layer 30, a polarizing film 33, an adhesive layer 31, and a transparent substrate 34 in this order.
[0253] The adhesive layers 30 and 31 are composed of the adhesive layers of the present invention, so even if the image display device 3 is placed under high temperature and high humidity conditions and then returns to room temperature, it is not easy to produce humidified white turbidity, and can maintain excellent visual recognition. It should be noted that one of the adhesive layers 30 and 31 may not be composed of the adhesive layer of the present invention.
[0254] The touch panel of the present invention is an image display device in which an optical member (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is incorporated.
[0255] Figure 4 It is a schematic diagram (cross-sectional view) showing a specific example of a preferred embodiment of the touch panel of the present invention.
[0256] exist Figure 4 In the figure, 4 represents a touch panel, 40 and 41 represent adhesive layers of the present invention, 42 represents an image display panel, 43 represents a touch sensor film, 44 represents a transparent substrate, and 45 represents a metal wiring. The touch panel 4 is stacked with an image display panel 42, an adhesive layer 40, a touch sensor film 43, an adhesive layer 41, and a transparent substrate 44 in this order.
[0257] The adhesive layers 40 and 41 are composed of the adhesive layers of the present invention, so even if the touch panel 4 is placed under high temperature and high humidity conditions and then returns to room temperature, it is not easy to produce humidified white turbidity, and can maintain excellent visual recognition. It should be noted that one of the adhesive layers 40 and 41 may not be composed of the adhesive layer of the present invention.
[0258] The method for forming the metal wiring on the touch sensor film is not particularly limited, and examples thereof include a method of removing a preliminarily provided metal layer by etching or the like, and a printing method.
[0259] The image display device and touch panel of the present invention may further include optical components such as a wavelength plate, a phase difference film, and an optical compensation film. These optical components may be single or multiple. There are no particular restrictions on the bonding method of these optical components, and examples thereof include: (1) bonding the optical component with an adhesive layer of the present invention to the adhesive sheet of the present invention; (2) bonding the optical component with an adhesive layer of the present invention to an adhesive sheet other than the adhesive sheet of the present invention, etc.
[0260] Example
[0261] Hereinafter, the present invention will be described in more detail based on examples, but the present invention is not limited to these examples. It should be noted that all blending parts (parts by weight) represent the blending parts of each component described.
[0262] [Manufacturing Example 1: Preparation of Prepolymer Composition A]
[0263] 0.04 parts by weight of a photopolymerization initiator (trade name "Omnirad 184", manufactured by IGM Resins BV) and 0.04 parts by weight of a photopolymerization initiator (trade name "Omnirad 651", manufactured by IGM Resins BV) were added to a monomer mixture consisting of 51.3 parts by weight of 2-ethylhexyl acrylate (2EHA), 26.6 parts by weight of isostearyl acrylate (ISTA), 21.0 parts by weight of N-vinyl-2-pyrrolidone (NVP) and 1.1 parts by weight of 4-hydroxybutyl acrylate (4-HBA), and then irradiated with ultraviolet rays until the viscosity (BH viscometer No. 5 rotor, 10 rpm, measuring temperature 30°C) reached about 20 Pa·s, thereby obtaining a prepolymer composition A in which part of the above-mentioned monomer components were polymerized.
[0264] [Manufacturing Example 2: Preparation of Prepolymer Composition B]
[0265] 0.09 parts by weight of a photopolymerization initiator (trade name "Omnirad 184", manufactured by IGM Resins BV) and 0.09 parts by weight of a photopolymerization initiator (trade name "Omnirad 651", manufactured by IGM Resins BV) were added to a monomer mixture consisting of 67 parts by weight of butyl acrylate (BA), 14 parts by weight of cyclohexyl acrylate (CHA) and 19 parts by weight of 4-hydroxybutyl acrylate (4-HBA), and then irradiated with ultraviolet rays until the viscosity (BH viscometer No. 5 rotor, 10 rpm, measuring temperature 30°C) reached about 20 Pa·s, thereby obtaining a prepolymer composition B in which part of the above-mentioned monomer components were polymerized.
[0266] [Production Example 3: Preparation of Prepolymer Composition C]
[0267] 0.04 parts by weight of a photopolymerization initiator (trade name "Omnirad 184", manufactured by IGM Resins BV) and 0.04 parts by weight of a photopolymerization initiator (trade name "Omnirad 651", manufactured by IGM Resins BV) were added to a monomer mixture consisting of 51.3 parts by weight of 2-ethylhexyl acrylate (2EHA), 26.6 parts by weight of isostearyl acrylate (ISTA), 15.5 parts by weight of N-vinyl-2-pyrrolidone (NVP) and 6.6 parts by weight of 4-hydroxybutyl acrylate (4-HBA), and then irradiated with ultraviolet rays until the viscosity (BH viscometer No. 5 rotor, 10 rpm, measuring temperature 30°C) reached about 20 Pa·s, thereby obtaining a prepolymer composition C in which part of the above-mentioned monomer components were polymerized.
[0268] [Example 1]
[0269] To 100 parts by weight of the prepolymer composition A obtained in Production Example 1 were added 1.66 parts by weight of hydrogenated 1,2-polybutadiene (trade name "BI-3000", number average molecular weight (Mn): 4750 (measured value), weight average molecular weight (Mw): 6150 (measured value), polydispersity (Mw / Mn): 1.30 (measured value), hydrogenation rate: 97% or more (catalog value), iodine value: 21 or less (catalog value), manufactured by Nippon Soda Co., Ltd.), 23.24 parts by weight of hydrogenated 1,2-polybutadiene diol (trade name "GI-2000", number average molecular weight (Mn): 4750 (measured value), weight average molecular weight (Mw): 6150 (measured value), polydispersity (Mw / Mn): 1.30 (measured value), hydrogenation rate: 97% or more (catalog value), iodine value: 21 or less (catalog value), manufactured by Nippon Soda Co., Ltd.), and 23.24 parts by weight of hydrogenated 1,2-polybutadiene diol (trade name "GI-2000", number average molecular weight (Mw): 6150 (measured value), polydispersity (Mw / Mn): 1.30 (measured value), hydrogenation rate: 97% or more (catalog value), iodine value: 21 or less (catalog value), manufactured by Nippon Soda Co., Ltd.). Average molecular weight (Mn): 3110 (measured value), weight average molecular weight (Mw): 5090 (measured value), polydispersity (Mw / Mn): 1.64 (measured value), hydrogenation rate: 93% or more (product catalog value), iodine value: 21 or less (product catalog value), manufactured by Nippon Soda Co., Ltd.), 0.08 weight parts of trimethylolpropane triacrylate (TMPTA), and 0.33 weight parts of silane coupling agent (trade name "KBM-403", manufactured by Shin-Etsu Chemical Co., Ltd.), and mixed to obtain an adhesive composition (pre-curing composition).
[0270] The above-mentioned adhesive composition was coated on a polyethylene terephthalate (PET) release liner (heavy release liner, trade name "MRF75", manufactured by Mitsubishi Resins Co., Ltd.) with a final thickness (thickness of the adhesive layer) of 250 μm to form a coating layer (adhesive composition layer). Next, a PET release liner (light release liner, trade name "MRE75", manufactured by Mitsubishi Resins Co., Ltd.) was set on the above-mentioned coating layer to cover the coating layer and block oxygen. Then, a laminate of MRF75 / coating layer (adhesive composition layer) / MRE75 was obtained.
[0271] Next, the laminate was irradiated with a black light (manufactured by Toshiba Corporation) from the upper surface (MRF38 side) of the laminate at an illumination of 5 mW / cm 2 The film was irradiated with ultraviolet light for 300 seconds. Then, it was dried in a 90°C dryer for 2 minutes to volatilize the residual monomers. Then, a substrate-free double-sided PSA sheet containing only the PSA layer and having both sides of the PSA layer protected by release liners was obtained.
[0272] [Example 2, Comparative Example 1]
[0273] A substrate-less double-sided PSA sheet was obtained in the same manner as in Example 1 except that the composition of the PSA composition and the thickness of the PSA layer were adjusted to those shown in Table 1.
[0274] [Table 1]
[0275]
[0276] The details of the components shown in Table 1 are as follows.
[0277] (Prepolymer composition)
[0278] A: Prepolymer composition A produced in Production Example 1
[0279] B: Prepolymer composition B produced in Production Example 2
[0280] C: Prepolymer composition C produced in Production Example 3
[0281] (monomer)
[0282] HEA: 2-Hydroxyethyl Acrylate
[0283] 4-HBA: 4-Hydroxybutyl acrylate
[0284] (Hydrogenated Polyolefin)
[0285] BI-3000: Trade name "BI-3000", hydrogenated 1,2-polybutadiene, number average molecular weight (Mn): 4750 (measured value), weight average molecular weight (Mw): 6150 (measured value), polydispersity (Mw / Mn): 1.30 (measured value), hydrogenation rate: 97% or more (product catalog value), iodine value: 21 or less (product catalog value), manufactured by Nippon Soda Co., Ltd.
[0286] GI-2000: Trade name "GI-2000", hydrogenated 1,2-polybutadiene diol, number average molecular weight (Mn): 3110 (measured value), weight average molecular weight (Mw): 5090 (measured value), polydispersity (Mw / Mn): 1.64 (measured value), hydrogenation rate: 97% or more (product catalog value), iodine value: 21 or less (product catalog value), manufactured by Nippon Soda Co., Ltd.
[0287] (Multifunctional acrylate)
[0288] TMPTA: Trimethylolpropane triacrylate
[0289] DPHA: Dipentaerythritol hexaacrylate
[0290] (Silane coupling agent)
[0291] KBM-403: Trade name "KBM-403", 3-glycidoxypropyltrimethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd.
[0292] The number average molecular weight (Mn), weight average molecular weight (Mw) and polydispersity (Mw / Mn) of the hydrogenated polyolefin and hydrogenated polyolefin diol were measured by GPC (gel permeation chromatography) under the following conditions and calculated in terms of polystyrene.
[0293] Analytical device: GPC: HLC-8320GPC (Tosoh)
[0294] Determination conditions:
[0295] Column: TSKgel Super HZM-H / HZ4000 / HZ3000 / HZ2000
[0296] Column size: 6.0mm I.D.×150mm
[0297] Eluent: THF (tetrahydrofuran)
[0298] Flow rate: 0.6mL / min
[0299] Detector: Differential Refractometer (RI)
[0300] Column temperature: 40°C
[0301] Injection volume: 20 μL
[0302] The molecular weight was calculated based on polystyrene conversion.
[0303] [Characteristics evaluation]
[0304] The substrate-free double-sided PSA sheets of Examples and Comparative Examples were subjected to the following measurements or evaluations.
[0305] (1) Measurement / evaluation of water content (W1, W2, W3) and humidification white turbidity
[0306] The substrate-free double-sided adhesive sheets of the examples and comparative examples were stored under the following storage conditions (A), (B), and (C), and then weighed and placed in a heating gasification device (manufactured by Nitto Seiko Analytical Science, Model VA-200). The gas generated by heating at 150° C. was introduced into a titration cell, and the water content (μg / cm 2 ).
[0307] (A) Water content after storage at 23°C and 50% RH for 24 hours: W1 (μg / cm 2 )
[0308] (B) After (A), the water content after being stored at 85°C, 85% RH for 8 hours and then at 23°C, 50% RH for 24 hours: W2 (μg / cm 2 )
[0309] (C) Water content after (A) at 85°C, 85% RH for 8 hours: W3 (μg / cm 2 )
[0310] Furthermore, the presence or absence of white turbidity (humidified white turbidity) in the samples after storage under the above condition (B) was visually evaluated.
[0311] (2) Determination of halogen ion content
[0312] The substrate-free double-sided PSA sheets of Examples and Comparative Examples were cut into pieces having a diameter of 10 mm or more and a thickness of 1 mm or more, and the release liner was peeled off to expose the surface of the PSA layer (sometimes referred to as "adhesive surface") to prepare test pieces.
[0313] The test piece was analyzed by an energy dispersive X-ray fluorescence analyzer (EDX-7000 manufactured by Shimadzu Corporation), and the halogen ion amount (ppm) was determined using a screening kit for the analyzer.
[0314] (3) Determination of acrylate ion content
[0315] The substrate-free double-sided adhesive sheets of the examples and comparative examples were cut into appropriate sizes, and the release liner was peeled off when provided, thereby exposing the surface of the adhesive layer (sometimes referred to as the "adhesive surface") to prepare test pieces. The size of the test piece (exposed area of the adhesive surface) was 100 cm 2.
[0316] Next, the test piece was placed in pure water at a temperature of 100° C. and boiled for 45 minutes to perform boiling extraction of acrylate ions and methacrylate ions.
[0317] Next, the total amount of acrylate ions and methacrylate ions in the extract obtained above was measured by ion chromatography (ion chromatography) (unit: ng), and the total amount of acrylate ions and methacrylate ions per unit area of the adhesive surface (exposed adhesive surface) of the test piece was calculated (unit: ng / cm 2 ). Regarding the measurement conditions of ion chromatography (ion chromatography), the measurement was performed under the following conditions.
[0318] [Measurement conditions of ion chromatography]
[0319] Analytical device: DX-320 manufactured by DIONEX
[0320] Separation column: Ion Pac AS15 (4 mm × 250 mm)
[0321] Guard column: Ion Pac AG15 (4mm×50mm)
[0322] Removal system: ASRS-ULTRA (external mode, 100mA)
[0323] Detector: Conductivity detector
[0324] Eluent: 7 mM KOH (0 min ~ 20 min)
[0325] 45mM KOH (20 minutes to 30 minutes)
[0326] (Using eluent generator EG40)
[0327] Eluent flow rate: 1.0ml / min
[0328] Injection volume: 250 μl
[0329] (4) Determination of dielectric constant
[0330] The adhesive layer obtained by peeling off the release liner from the substrate-free double-sided adhesive sheet obtained in the example or comparative example was sandwiched between a copper foil and an electrode, and the relative dielectric constant at a frequency of 100 kHz was measured using the following apparatus. In the measurement, three samples were prepared, and the average value of the measured values of these three samples was taken as the relative dielectric constant.
[0331] In addition, the relative dielectric constant of the adhesive layer at a frequency of 100 kHz was measured according to JIS K 6911 under the following conditions.
[0332] Measurement method: capacitance method (device: Agilent Technologies 4294A precision impedance analyzer)
[0333] Electrode structure: 12.1mmφ, 0.5mm thick aluminum plate
[0334] Counter electrode: 3oz copper plate
[0335] Measurement environment: 23℃±1℃, 52%±1%RH
[0336] [Table 2]
[0337]
[0338] Modifications of the present invention will be described below.
[0339] [Note 1]
[0340] An acrylic adhesive composition for forming an adhesive layer used for bonding an optical member of an image display device, wherein:
[0341] The water contents W1 and W2 after the following conditions (A) and (B) are applied to the adhesive layer satisfy the following formula (1):
[0342] W2 / W1>1 …… (1)
[0343] (A) Water content of the adhesive layer after being stored at 23°C and 50% RH for 24 hours: W1 (μg / cm 2 )
[0344] (B) Water content of the adhesive layer after (A) when it was stored at 85°C and 85% RH for 8 hours and then at 23°C and 50% RH for 24 hours: W2 (μg / cm 2 ).
[0345] [Note 2]
[0346] The acrylic adhesive composition according to Supplement 1, wherein the water contents W1 and W3 after the following conditions (A) and (C) are applied to the adhesive layer satisfy the following formula (2):
[0347] W3 / W1>2.3 …… (2)
[0348] (A) Water content of the adhesive layer after being stored at 23°C and 50% RH for 24 hours: W1 (μg / cm 2 )
[0349] (C) Water content of the adhesive layer after (A) after being stored at 85°C and 85% RH for 8 hours: W3 (μg / cm 2 ).
[0350] [Note 3]
[0351] The acrylic pressure-sensitive adhesive composition according to Appendix 1 or 2, wherein the acrylic pressure-sensitive adhesive composition contains an acrylic polymer,
[0352] The acrylic polymer contains 10 to 40 parts by weight of the functional group-containing monomer based on the total amount (100 parts by weight) of monomer components constituting the acrylic polymer.
[0353] [Note 4]
[0354] The acrylic pressure-sensitive adhesive composition according to any one of Appendixes 1 to 3, wherein the halogen ion concentration of the acrylic pressure-sensitive adhesive composition is 50 ppm or less.
[0355] [Note 5]
[0356] A pressure-sensitive adhesive layer, comprising the acrylic pressure-sensitive adhesive composition according to any one of Appendix 1 to 4.
[0357] [Note 6]
[0358] The adhesive layer according to Supplementary Note 5, wherein the dielectric constant of the adhesive layer at a frequency of 100 kHz is 4 or less.
[0359] [Note 7]
[0360] A pressure-sensitive adhesive sheet comprising the pressure-sensitive adhesive layer according to Supplementary Note 5 or 6.
[0361] [Note 8]
[0362] An optical member with a pressure-sensitive adhesive layer, wherein the pressure-sensitive adhesive sheet according to Supplementary Note 7 is adhered to at least one surface of the optical member.
[0363] [Note 9]
[0364] An image display device comprising the pressure-sensitive adhesive layer-attached optical member according to Supplementary Note 8.
[0365] [Note 10]
[0366] The image display device according to Supplementary Note 9, wherein the image display device is a touch panel.
[0367] Description of symbols
[0368] 1 Adhesive sheet
[0369] 10 Adhesive layer
[0370] 11, 12 Release liner
[0371] 2A Optical member with adhesive layer
[0372] 2B Touch sensor film with adhesive layer
[0373] 20 Adhesive layer
[0374] 21 Optical components
[0375] 22 Release liner
[0376] 23 Touch sensor film
[0377] 24 Metal wiring
[0378] 3 Image display device
[0379] 30, 31 Adhesive layer
[0380] 32 Image display panel
[0381] 33 Polarizing film
[0382] 34 transparent substrate
[0383] 4 Touch Panel
[0384] 40, 41 Adhesive layer
[0385] 42 Image display panel
[0386] 43 Touch sensor film
[0387] 44 transparent substrate
[0388] 45 Metal wiring
Claims
1. An acrylic adhesive composition for forming an adhesive layer used for bonding an optical member of an image display device, wherein: The water contents W1 and W2 after the following conditions (A) and (B) are applied to the adhesive layer satisfy the following formula (1): W2 / W1>1 …… (1) (A) Water content of the adhesive layer after being stored at 23°C and 50% RH for 24 hours: W1 (μg / cm 2 ) (B) Water content of the adhesive layer after (A) when it was stored at 85°C and 85% RH for 8 hours and then at 23°C and 50% RH for 24 hours: W2 (μg / cm 2 ).
2. The acrylic adhesive composition according to claim 1, wherein The water contents W1 and W3 after the following conditions (A) and (C) are applied to the adhesive layer satisfy the following formula (2): W3 / W1>2.3 …… (2) (A) Water content of the adhesive layer after being stored at 23°C and 50% RH for 24 hours: W1 (μg / cm 2 ) (C) Water content of the adhesive layer after (A) after being stored at 85°C and 85% RH for 8 hours: W3 (μg / cm 2 ).
3. The acrylic adhesive composition according to claim 1 or 2, wherein: The acrylic adhesive composition contains an acrylic polymer. The acrylic polymer contains 10 to 40 parts by weight of the functional group-containing monomer based on the total amount (100 parts by weight) of monomer components constituting the acrylic polymer.
4. The acrylic pressure-sensitive adhesive composition according to any one of claims 1 to 3, wherein The acrylic pressure-sensitive adhesive composition has a halogen ion concentration of 50 ppm or less.
5. An adhesive layer, wherein: The pressure-sensitive adhesive layer is formed from the acrylic pressure-sensitive adhesive composition according to any one of claims 1 to 4.
6. The adhesive layer according to claim 5, wherein The adhesive layer has a dielectric constant of 4 or less at a frequency of 100 kHz.
7. An adhesive sheet, wherein: The pressure-sensitive adhesive sheet comprises the pressure-sensitive adhesive layer according to claim 5 or 6.
8. An optical member with an adhesive layer, wherein: The pressure-sensitive adhesive sheet according to claim 7 is adhered to at least one surface of the optical member.
9. An image display device, wherein: The image display device comprises the pressure-sensitive adhesive layer-attached optical member according to claim 8 .
10. The image display device according to claim 9, wherein: The image display device is a touch panel.
Citation Information
Patent Citations
Acrylic adhesives and its production method
JP2002069411A
Adhesive double coated sheet and method of affixing touch panel to display device
JP2003238915A
Double-sided adhesive sheet and display device with touch panel
JP2003342542A
Pressure sensitive adhesive double-sided sheet and display device with touch panel
JP2004231723A